Gas Barrier Film

JP7639342B2Active Publication Date: 2025-03-05TOPPAN HOLDINGS INC
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2020559991
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-02
Filing Date
2019-12-05
Publication Date
2025-03-05
Estimated Expiration
2039-12-05

AI Technical Summary

Benefits of technology

【0008】 本発明のガスバリア性フィルムは、酸素バリア性を付与するための皮膜の厚みが薄くても、本来の酸素バリア性を充分に発現でき、酸素バリア性に優れる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639342000007
    Figure 0007639342000007
  • Figure 0007639342000008
    Figure 0007639342000008
  • Figure 0007639342000009
    Figure 0007639342000009
Patent Text Reader

Abstract

The gas barrier film has a resin substrate and an oxygen barrier coating located in contact with a first surface of the resin substrate. The resin substrate has two or more resin layers including a base layer. Of the two or more resin layers, the resin layer forming the first surface of the resin substrate does not contain an antiblocking agent.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a gas barrier film. This application claims priority to Japanese Patent Application No. 2018-228408 filed on December 5, 2018, and Japanese Patent Application No. 2019-159373 filed on September 2, 2019, the contents of which are incorporated herein by reference. [Background technology]

[0002] Packaging materials used for packaging food, medicine, etc. are required to have the property of preventing the intrusion of gases (water vapor, oxygen, etc.) that denature the contents, in order to prevent deterioration or spoilage of the contents and to maintain their function and quality. For this reason, film materials with gas barrier properties (gas barrier films) are used for these packaging materials.

[0003] A known gas barrier film is one in which a gas barrier layer made of a material having gas barrier properties is provided on the surface of a resin substrate. Known gas barrier layers include metal foils, metal deposition films, and films formed by wet coating. Known films that exhibit oxygen barrier properties include resin films formed from a coating agent containing a resin such as a water-soluble polymer or polyvinylidene chloride, and inorganic layered mineral composite resin films formed from a coating agent containing a water-soluble polymer and an inorganic layered mineral (Patent Document 1). Furthermore, as a gas barrier layer, a gas barrier layer formed by sequentially laminating a vapor-deposited thin film layer made of an inorganic oxide and a gas barrier composite coating containing an aqueous polymer, an inorganic layered compound, and a metal alkoxide (Patent Document 2) and a gas barrier layer containing a polyvalent metal salt of a carboxylic acid, which is a reaction product between a carboxy group of a polycarboxylic acid polymer and a polyvalent metal compound (Patent Document 3) have been proposed. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent No. 6176239 [Patent Document 2] Japanese Patent Publication No. 2000-254994 [Patent Document 3] Japanese Patent No. 4373797 Summary of the Invention [Problem to be solved by the invention]

[0005] Gas barrier films in which a coating is provided on the surface of a resin substrate by a wet coating method, a vapor deposition method, a sputtering method, or the like, sometimes have unstable oxygen barrier properties depending on the production lot. Specifically, the oxygen barrier properties of the gas barrier films sometimes are inferior to the inherent oxygen barrier properties, that is, the oxygen barrier properties expected from the material constituting the coating and the thickness of the coating. In particular, such problems tend to occur more easily when the coating is thinner.

[0006] An object of the present invention is to provide a gas barrier film having excellent oxygen barrier properties, which can fully exhibit the inherent oxygen barrier properties even when the thickness of the film for imparting oxygen barrier properties is thin. [Means for solving the problem]

[0007] The present invention includes the following aspects. [1] A resin substrate and an oxygen barrier coating formed on a first surface of the resin substrate and a heat-sealable heat-adhesive layer. between the resin substrate and the oxygen barrier film. The inorganic oxide layer is formed of aluminum oxide or silicon oxide. A gas barrier film, wherein the oxygen barrier coating contains at least one of a metal alkoxide, a hydrolysate of a metal alkoxide, and a reaction product of a metal alkoxide, and a water-soluble polymer, and does not contain an inorganic layered compound, and the resin substrate has two or more resin layers, and of the two or more resin layers, a resin layer forming a first surface does not contain an antiblocking agent. Effect of the Invention

[0008] The gas barrier film of the present invention is excellent in oxygen barrier property because it can fully exhibit the inherent oxygen barrier property even if the thickness of the coating for imparting oxygen barrier property is thin. [Brief description of the drawings]

[0009] [Figure 1] 1 is a schematic cross-sectional view of a gas barrier film according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a gas barrier film according to a second embodiment of the present invention. [Diagram 3] 1 is a cross-sectional image of a gas barrier film according to a comparative example obtained by a scanning electron microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In order to investigate the cause of the above-mentioned problem, the present inventors used an electron microscope to observe the surface and cross section of a gas barrier film with poor oxygen barrier properties. At the location where an antiblocking agent (hereinafter also referred to as "AB agent"), which is added to prevent blocking of the resin substrate, was present, the inventors performed electron microscope observation of the cross section using a focused ion / electron beam processing observation device, and confirmed that defects several μm in width had occurred in the film at the location where the AB agent was present. It was believed that these defects became paths for gas permeation, and thus the oxygen barrier properties were not fully expressed. There are protrusions on the surface of the resin substrate due to the AB agent. When the coating agent was applied, the coating film was not formed locally at the protrusions, which is thought to have caused the defects.

[0011] Each embodiment of the present invention is based on the above findings. A first embodiment of the present invention will be described below with reference to FIG. FIG. 1 is a schematic cross-sectional view of a gas barrier film 10 according to a first embodiment. The gas barrier film 10 comprises a resin substrate 1 and a coating 5 (oxygen barrier coating). The film 5 is located in contact with the first surface 1 a of the resin substrate 1 .

[0012] (Resin substrate) The resin substrate 1 has two or more resin layers including a base layer 4. Specifically, the resin substrate 1 has the base layer 4, a front layer 2 located on one side of the base layer 4, and a back layer 3 located on the other side of the base layer 4. The surface layer 2 constitutes a first surface 1 a of the resin substrate 1 . The back layer 3 constitutes the second surface 1b of the resin substrate 1 opposite to the first surface 1a. The resin substrate 1 contains a resin, and each of the front layer 2, back layer 3, and base layer 4 that constitute the resin substrate 1 also contains a resin.

[0013] The base layer 4 adjusts the mechanical properties, chemical properties, thermal properties, optical properties, etc. of the resin substrate 1. Mechanical properties include rigidity, elongation, stiffness, tear strength, impact strength, puncture strength, pinhole resistance, etc. Chemical properties include water vapor barrier properties, gas barrier properties, aroma retention, chemical resistance, oil resistance, etc. Thermal properties include melting point, glass transition point, heat resistance, cold resistance, thermal shrinkage rate, etc. Optical properties include transparency, gloss, etc.

[0014] From the viewpoints of ease of availability and water vapor barrier properties, a polyolefin resin is preferable as the resin used as the raw material of the base layer 4. That is, the resin substrate 1 is preferably a polyolefin resin substrate. Examples of polyolefin resins include polyethylene and polypropylene. Polypropylene may be a homopolymer, a random copolymer, or a block copolymer. A homopolymer is a polypropylene consisting of only propylene alone. A random copolymer is a polypropylene in which the main monomer propylene and a different type of comonomer are randomly copolymerized to form a homogeneous phase. A block copolymer is a polypropylene in which the main monomer propylene and the above comonomer are copolymerized in blocks or polymerized in a rubber-like form to form a heterogeneous phase. Any one of these polyolefin resins may be used alone, or two or more may be blended together.

[0015] The base layer 4 may contain additives. The additives can be appropriately selected from various known additives. Examples of the additives include antiblocking agents (AB agents), heat stabilizers, weather stabilizers, ultraviolet absorbers, lubricants, slipping agents, nucleating agents, antistatic agents, antifogging agents, pigments, and dyes. Any one of these additives may be used alone, or two or more may be used in combination. Among the above, lubricants and slipping agents are preferred from the viewpoint of suitability for processing. The content of the additive in the base layer 4 can be appropriately adjusted within a range that does not impair the effects of the present invention. The base layer 4 typically does not contain an AB agent.

[0016] The base layer 4 may be of a single layer or multi-layer structure. The thickness of the base layer 4 may be, for example, 3 to 200 μm, or may be 6 to 30 μm.

[0017] The resin constituting the surface layer 2 may be the same as or different from the resin constituting the base layer 4. For example, when the resins constituting each of the surface layer 2 and the base layer 4 are polyolefin-based resins, the polyolefin-based resin constituting the surface layer 2 may be a polyolefin-based resin having a lower melting point than the polyolefin-based resin constituting the base layer 4. This is to improve the adhesion between the resin substrate 1 and the film 5. Examples of polyolefin-based resins that can be used for the surface layer 2 include ethylene-1-butene copolymers, ethylene-propylene-1-butene copolymers, ethylene-acrylic acid copolymers, ionomers obtained by crosslinking ethylene-acrylic acid copolymers with metal ions, polypropylene, poly(1-butene), 1-butene-ethylene copolymers, propylene-ethylene copolymers, propylene-1-butene copolymers, and propylene-pentene copolymers. Any one of these resins may be used alone, or two or more may be blended together.

[0018] The surface layer 2 does not contain an AB agent. Since the surface layer 2 does not contain an AB agent, there are no protrusions resulting from the AB agent on the first surface 1a of the resin substrate 1. Therefore, when the coating 5 is formed by a wet coating method, the occurrence of defects that serve as paths for gas permeation can be suppressed, and excellent oxygen barrier properties are exhibited.

[0019] The surface layer 2 may contain additives other than the AB agent. The additives can be appropriately selected from various known additives. Examples of the additives include heat stabilizers, weather stabilizers, ultraviolet absorbers, lubricants, slipping agents, nucleating agents, antistatic agents, antifogging agents, pigments, and dyes. Any one of these additives may be used alone, or two or more may be used in combination. Among the above, lubricants and slipping agents are preferred from the viewpoint of processing suitability. The content of the additive in the surface layer 2 can be appropriately adjusted within a range that does not impair the effects of the present invention.

[0020] The thickness of the surface layer 2 may be, for example, 0.1 to 10 μm, or may be 0.5 to 5.0 μm.

[0021] The resin constituting the back layer 3 may be the same as or different from the resin constituting the base layer 4, similar to the resin constituting the surface layer 2. For example, when the resins constituting each of the back layer 3 and the base layer 4 are polyolefin-based resins, the polyolefin-based resin constituting the back layer 3 may be a polyolefin-based resin having a lower melting point than the polyolefin-based resin constituting the base layer 4. Examples of polyolefin-based resins that can be used for the back layer 3 include those listed as polyolefin-based resins that can be used for the surface layer 2.

[0022] The back layer 3 contains an AB agent 6, as shown in FIG. Since the back layer 3 contains the AB agent 6, protrusions resulting from the AB agent 6 are locally present on the second surface 1b of the resin substrate 1. These protrusions can suppress blocking of the resin substrate 1 and the gas barrier film 10. On the second surface 1b, the AB agent 6 may be exposed or may be covered with a resin.

[0023] The AB agent 6 is a solid particle, and examples thereof include organic particles and inorganic particles. Examples of organic particles include polymethyl methacrylate particles, polystyrene particles, and polyamide particles. These organic particles are obtained, for example, by emulsion polymerization or suspension polymerization. Examples of inorganic particles include silica particles, zeolite, talc, kaolinite, and feldspar. These AB agents may be used alone or in combination of two or more. As the AB agent 6, polymethyl methacrylate particles are preferred for organic systems, and silica particles are preferred for inorganic systems.

[0024] The average particle size of the AB agent 6 is typically equal to or less than the thickness of the back layer 3. In consideration of the appearance of the second surface 1b, the transparency of the back layer 3, the possibility of the AB agent 6 falling off, and the anti-blocking performance, the average particle size of the AB agent 6 is preferably 0.1 μm or more and 5 μm or less. In the gas barrier film 10, the front layer 2 does not contain the AB agent 6. Therefore, it is preferable that the anti-blocking performance of the AB agent 6 in the back layer 3 is high. From the viewpoint of anti-blocking performance, it is particularly preferable that the average particle size of the AB agent 6 is 2 μm or more and 5 μm or less. The average particle size of the AB agent 6 is measured by the Coulter method.

[0025] The amount of the AB agent 6 added to the back layer 3 is, for example, 0.1 to 0.4% by mass relative to the total mass of the back layer 3. The amount of the AB agent 6 added to the back layer 3 is specifically calculated by the following formula. Amount of AB agent added [mass%] = {(i) / 100} × {(ii) / 100} × 100 In the formula, (i) indicates the concentration (mass %) of the AB agent in the masterbatch resin chips obtained by adding the AB agent to a resin, stirring the mixture, feeding the mixture into an extruder and kneading the mixture, and forming the mixture into pellets by melt extrusion. (ii) indicates the concentration (mass %) of masterbatch resin chips containing an AB agent relative to the total mass of the resin pellets constituting the back layer 3 when the masterbatch resin chips containing an AB agent are blended with a resin not containing an AB agent.

[0026] The back layer 3 may contain additives other than the AB agent. Examples of additives include the same additives as those described above. The content of the additives in the back layer 3 can be appropriately adjusted within a range that does not impair the effects of the present invention.

[0027] The thickness of the back layer 3 may be, for example, 0.1 to 10 μm, or may further be 0.5 to 5.0 μm. The thickness of the back layer 3 is the thickness of a portion where the protrusions resulting from the AB agent 6 are not present.

[0028] The resin substrate 1 is preferably a coextruded film in which the front layer 2, back layer 3, and base layer 4 are laminated by coextrusion. The resin substrate 1 may be a stretched film or an unstretched film.

[0029] The resin substrate 1 preferably has a biaxially oriented polypropylene film. Since biaxially oriented polypropylene films are particularly excellent in water vapor barrier performance, the gas barrier film 10 has improved water vapor barrier properties by having the biaxially oriented polypropylene film. The biaxially oriented polypropylene film may be at least one of a homopolymer, a random copolymer, a block copolymer, etc., processed into a film shape. The biaxially oriented polypropylene film is preferably a coextruded film.

[0030] The resin substrate having the biaxially oriented polyolefin film may be made of a biaxially oriented polypropylene film, or may be a laminate of a biaxially oriented polypropylene film and another resin film. Examples of the other resin film include polyester films such as polyethylene terephthalate and polyethylene naphthalate, polyolefin resin films such as polyethylene, polystyrene films, polyamide films such as nylon, polycarbonate films, polyacrylonitrile films, and engineering plastic films such as polyimide films.

[0031] The thickness of the resin substrate 1 can be adjusted depending on the application, the desired properties, etc., and is not particularly limited, but may be, for example, 3 to 200 μm, or may further be 6 to 30 μm. The thickness of the resin substrate 1 is the thickness of a portion where no protrusions resulting from the AB agent 6 exist.

[0032] The surfaces (first surface 1a and second surface 1b) of the resin substrate 1 may be subjected to at least one treatment selected from the group consisting of chemical treatment, solvent treatment, corona treatment, plasma treatment and ozone treatment.

[0033] (Oxygen barrier film) The film 5 may be a known oxygen barrier film formed by a wet coating method. The film 5 is obtained by forming a coating film made of a coating agent on the first surface a of the resin substrate 1 by a wet coating method and drying the coating film. The coating film is a wet film, and the film is a dry film.

[0034] The coating 5 is preferably a coating (inorganic layered mineral composite resin film) formed from a coating agent containing a water-soluble polymer and an inorganic layered mineral. A gas barrier film having an inorganic layered mineral composite resin film as a gas barrier layer has advantages such as excellent oxygen barrier properties even in a high humidity atmosphere, sufficient adhesion strength to other materials and film cohesion strength as a packaging material, transparency and stretch resistance not found in metal foils or metal vapor deposition films, and no risk of generating harmful substances such as dioxins. The coating agent will be described in detail later.

[0035] The thickness of the film 5, that is, the thickness of the film made of the coating agent after drying, is set according to the required oxygen barrier properties and may be, for example, 0.2 to 5 μm. The thickness of the film 5 is preferably 0.2 to 0.7 μm, and more preferably 0.3 to 0.5 μm. If the thickness of the film 5 is 0.2 μm or more, sufficient oxygen barrier properties are easily obtained. If the thickness of the coating 5 is 0.7 μm or less, the presence or absence of protrusions derived from the AB agent on the first surface 1a has a large effect on the oxygen barrier property, and the present invention is highly useful. Furthermore, if the thickness of the coating 5 is 0.7 μm or less, it is easy to form a uniform coated surface, and the drying load and manufacturing costs can be suppressed.

[0036] (Method of manufacturing gas barrier film) The gas barrier film 10 can be produced by forming a coating 5 on the first surface a of a resin substrate 1 . As the resin substrate 1, a commercially available product may be used, or one produced by a known method may be used. As described above, the film 5 is obtained by forming a coating film made of a coating agent on the first surface a of the resin substrate 1 by a wet coating method, and drying this coating film. As the wet coating method, known wet coating methods such as roll coating, gravure coating, reverse coating, die coating, screen printing, and spray coating can be used. The method for drying the coating film made of the coating agent can be a known drying method such as hot air drying, hot roll drying, infrared irradiation, etc. The drying conditions can be, for example, 90° C. for 10 seconds.

[0037] (Coating agent) As described above, a preferred embodiment of the coating agent is a coating agent that contains a water-soluble polymer and an inorganic layered mineral. The coating agent of this embodiment typically further contains an aqueous medium. The coating agent of this embodiment preferably further contains an aqueous polyurethane resin. The coating agent of this embodiment preferably further contains a curing agent. The coating agent of this embodiment may further contain other components as necessary.

[0038] <Water-soluble polymer> A water-soluble polymer is a polymer that can be dissolved in water. Dissolution here refers to a state in which the polymer, although a solute, is dispersed at the molecular chain level in the solvent water to form a homogeneous system. More specifically, it refers to a state in which the intermolecular forces between the polymer chains and the water molecules are stronger than the intermolecular forces between the polymer chains, causing the polymer chains to become disentangled and dispersed uniformly in the water.

[0039] The water-soluble polymer is not particularly limited as long as it is a compound capable of penetrating between unit crystals of the inorganic layered mineral and coordinating (intercalating). Specific examples of water-soluble polymers include polyvinyl alcohol resins (polyvinyl alcohol and its derivatives, etc.), other vinyl polymers (polyvinylpyrrolidone, polyacrylic acid, polymethacrylic acid, or their esters, salts, and copolymers thereof, polyhydroxyethyl methacrylate and its copolymers, etc.), cellulose derivatives (carboxymethyl cellulose, hydroxyethyl cellulose, etc.), starches (oxidized starch, etherified starch, dextrin, etc.), copolymer polyesters having polar groups (polyesters containing a sulfoisophthalic acid structure, etc.), urethane polymers, and functional group-modified polymers in which the carboxyl groups of these various polymers have been modified, etc. Taking into consideration the film coagulation rate, the water-soluble polymer preferably has a degree of polymerization of 200 or more. The coating agent of this embodiment may contain one type of water-soluble polymer, or two or more types of water-soluble polymers.

[0040] The water-soluble polymer preferably contains at least one polyvinyl alcohol resin selected from the group consisting of polyvinyl alcohol polymers and their derivatives, and particularly preferably contains a polyvinyl alcohol resin having a degree of saponification of 95% or more and a degree of polymerization of 300 or more. The degree of polymerization of the polyvinyl alcohol resin is preferably 300 to 2400, and particularly preferably 450 to 2000. The higher the degree of saponification or polymerization of the polyvinyl alcohol resin, the lower the moisture absorption swelling property and the higher the gas barrier property it exhibits. If the degree of saponification of the polyvinyl alcohol resin is 95% or more, sufficient gas barrier property is easily obtained. In addition, if the degree of polymerization of the polyvinyl alcohol resin is 300 or more, the oxygen barrier property and the film cohesive strength are excellent. On the other hand, if the degree of polymerization is 2400 or less, the viscosity of the coating agent is sufficiently low, it is easy to mix uniformly with other components, and problems such as a decrease in gas barrier property and adhesion strength are unlikely to occur.

[0041] <Inorganic layered minerals> The inorganic layered mineral refers to an inorganic compound in which extremely thin unit crystal layers are stacked to form a single layered particle. As the inorganic layered mineral, a compound that swells and / or cleaves in water is preferred, and among them, a clay compound that has swelling properties in water is preferred. More specifically, the inorganic layered mineral is preferably a clay compound that has the property of absorbing and / or swelling water by coordinating it between the unit crystal layers. Such a clay compound is generally a compound containing Si 4+ O 2- The layers are coordinated to form a tetrahedral structure, and the Al 3+ , Mg 2+ , Fe 2+ , Fe 3+ etc. 2- and O.H. - The layers that form the octahedral structure are bonded to each other in a 1:1 or 2:1 ratio and stacked to form a layered structure. The clay compound may be a natural compound or a synthetic compound.

[0042] Representative examples of inorganic layered minerals include hydrated silicates such as phyllosilicate minerals, such as kaolinite group clay minerals such as halloysite, kaolinite, endelite, dickite, and nacrite, antigorite group clay minerals such as antigorite and chrysotile, smectite group clay minerals such as montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, and stevensite, vermiculite group clay minerals such as vermiculite, and mica or mica group clay minerals such as muscovite, phlogopite, margarite, tetrasilylic mica, and taeniolite. These inorganic layered minerals may be used alone or in combination of two or more. As the inorganic layered minerals, smectite clay minerals such as montmorillonite, and mica clay minerals such as water-swellable mica are particularly preferred.

[0043] The size of the inorganic layered mineral is preferably an average particle size of 10 μm or less and a thickness of 500 nm or less. If the average particle size is 10 μm or less and the thickness is 500 nm or less, the inorganic layered mineral tends to be uniformly aligned in the film formed from the coating agent, and the gas barrier property and film cohesive strength are improved. The lower limit of the average particle size of the inorganic layered mineral is, for example, 1 μm. The lower limit of the thickness of the inorganic layered mineral is, for example, 10 nm. The average particle size of the inorganic layered mineral is measured by a laser diffraction particle size distribution analyzer. The thickness of the inorganic layered minerals is measured by atomic force microscopy (AFM).

[0044] It is particularly preferable that the inorganic layered mineral contains at least water-swellable synthetic mica having an average particle size of 1 to 10 μm and a thickness of 10 to 100 nm. Water-swellable synthetic mica has high compatibility with water-soluble polymers and aqueous polyurethane resins, and contains fewer impurities than natural mica. Therefore, when water-swellable synthetic mica is used as the inorganic layered mineral, it is difficult to cause a decrease in gas barrier properties and a decrease in film cohesion due to impurities. In addition, since water-swellable synthetic mica has fluorine atoms in its crystal structure, it also contributes to suppressing the humidity dependency of the gas barrier properties of the film formed from the coating agent. In addition, since water-swellable synthetic mica has a higher aspect ratio than other water-swellable inorganic layered minerals, the labyrinth effect works more effectively, and the gas barrier properties of the film formed from the coating agent are particularly highly expressed.

[0045] <Aqueous medium> The aqueous medium may be water, a water-soluble or hydrophilic organic solvent, or a mixture thereof. The aqueous medium is usually water or a medium containing water as a main component. The water content in the aqueous medium is preferably 70% by mass or more, and more preferably 80% by mass or more. Examples of water-soluble or hydrophilic organic solvents include alcohols such as methanol, ethanol, and isopropanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran; cellosolves, carbitols, and nitriles such as acetonitrile. When the coating agent contains an aqueous polyurethane resin, the aqueous medium may or may not contain a neutralizing agent (base) that neutralizes the acid groups. Usually, a neutralizing agent is contained.

[0046] <Water-based polyurethane resin> The aqueous polyurethane resin contains a polyurethane resin having an acid group (hereinafter also referred to as an "acid group-containing polyurethane resin") and a polyamine compound. If the coating agent contains an aqueous polyurethane resin, the coating agent has excellent wettability to the resin substrate 1, and the film formed from the coating agent has excellent adhesive strength to the resin substrate 1. Furthermore, if the aqueous polyurethane resin contains an acid group-containing polyurethane resin and a polyamine compound, it will exhibit excellent oxygen barrier properties even in a high humidity atmosphere.

[0047] The acid group of the acid group-containing polyurethane resin (anionic self-emulsifying polyurethane resin) constituting the aqueous polyurethane resin can be bonded to the amino group (primary amino group, secondary amino group, tertiary amino group, etc.) of the polyamine compound constituting the aqueous polyurethane resin. Examples of the acid group include a carboxyl group and a sulfonic acid group. The acid group can usually be neutralized with a neutralizing agent (base) and may form a salt with a base. The acid group may be located at the end of the acid group-containing polyurethane resin or at the side chain, but is preferably located at least at the side chain.

[0048] The acid value of the acid group-containing polyurethane resin can be selected within a range that can impart water solubility or water dispersibility, but is usually 5 to 100 mgKOH / g, preferably 10 to 70 mgKOH / g, and more preferably 15 to 60 mgKOH / g. If the acid value of the acid group-containing polyurethane resin is less than 5 mgKOH / g, the water solubility or water dispersibility of the acid group-containing polyurethane resin becomes insufficient, which may cause a decrease in the uniform dispersion of the aqueous polyurethane resin and other materials and a decrease in the dispersion stability of the coating agent. If the acid value of the acid group-containing polyurethane resin is more than 100 mgKOH / g, this may cause a decrease in the water resistance and oxygen barrier properties of the film formed from the coating agent. Therefore, by having the acid value of the acid group-containing polyurethane resin be within the range of 5 to 100 mgKOH / g, a decrease in the dispersion stability of the coating agent and a decrease in the water resistance and oxygen barrier properties of the film formed from the coating agent can be avoided. The acid value of the acid group-containing polyurethane resin is measured by a method in accordance with JIS K0070.

[0049] The total of the urethane group concentration and the urea group concentration of the acid group-containing polyurethane resin is preferably 15 to 60 mass% or more, and more preferably 20 to 60 mass%. If the total of the urethane group concentration and the urea group concentration is 15 mass% or more, the oxygen barrier property of the film formed from the coating agent is more excellent. If the total of the urethane group concentration and the urea group concentration is 60 mass% or less, the flexibility of the film formed from the coating agent is more excellent. The urethane group concentration means the ratio of the molecular weight of the urethane group (59 g / equivalent) to the molecular weight of the repeating constitutional unit of the polyurethane resin. The urea group concentration means the ratio of the molecular weight of the urea group (primary amino group (amino group): 58 g / equivalent, secondary amino group (imino group): 57 g / equivalent) to the molecular weight of the repeating structural unit of the polyurethane resin. When a mixture of two or more types of acid group-containing polyurethane resin is used, the urethane group concentration and urea group concentration can be calculated based on the charge of the reaction components, that is, the proportion of each component used.

[0050] An acid group-containing polyurethane resin usually has at least a rigid unit (a unit composed of a hydrocarbon ring) and a short-chain unit (for example, a unit composed of a hydrocarbon chain). That is, the repeating unit of an acid group-containing polyurethane resin usually includes a hydrocarbon ring (at least one of an aromatic and a non-aromatic hydrocarbon ring) derived from a polyisocyanate component, a polyhydroxy acid component, a polyol component, or a chain extender component (particularly, at least a polyisocyanate component).

[0051] The proportion of units constituted by hydrocarbon rings in the repeating structural units of the acid group-containing polyurethane resin is usually 10 to 70 mass%, preferably 15 to 65 mass%, and more preferably 20 to 60 mass%. If the proportion of units constituted by hydrocarbon rings in the repeating structural units of the acid group-containing polyurethane resin is 10 mass% or more, the oxygen barrier properties of the film formed from the coating agent are more excellent. If the proportion of units constituted by hydrocarbon rings in the repeating structural units of the acid group-containing polyurethane resin is 70 mass% or less, the flexibility of the film formed from the coating agent is more excellent.

[0052] The number average molecular weight of the acid group-containing polyurethane resin can be appropriately selected, but is preferably 800 to 1,000,000, more preferably 800 to 200,000, and even more preferably 800 to 100,000. If the number average molecular weight of the acid group-containing polyurethane resin is 1,000,000 or less, the viscosity increase of the coating agent can be suppressed. If the number average molecular weight of the acid group-containing polyurethane resin is 800 or more, the oxygen barrier property of the film formed from the coating agent is more excellent. The number average molecular weight of the acid group-containing polyurethane resin is a value calculated as standard polystyrene, measured by gel permeation chromatography (GPC).

[0053] The acid group-containing polyurethane resin may be crystalline in order to enhance the oxygen barrier property. The glass transition point of the acid group-containing polyurethane resin is preferably 100° C. or higher, more preferably 110° C. or higher, and even more preferably 120° C. or higher. If the acid group-containing polyurethane resin has a glass transition point of 100° C. or higher, the film formed from the coating agent has better oxygen barrier properties. The glass transition point of the acid group-containing polyurethane resin is typically 200° C. or lower, further 180° C. or lower, and further 150° C. or lower. When the above-mentioned preferable ranges are satisfied, it is substantially unlikely that the glass transition point of the acid group-containing polyurethane resin will be higher than 200° C. Therefore, the glass transition point of the acid group-containing polyurethane resin is preferably from 100 to 200°C, more preferably from 110 to 180°C, and even more preferably from 120 to 150°C. The glass transition point of the acid group-containing polyurethane resin is measured by differential scanning calorimetry (DSC).

[0054] In the case of an aqueous polyurethane resin, oxygen barrier properties are developed by bonding the acid groups of the acid group-containing polyurethane resin with a polyamine compound acting as a crosslinking agent. The polyamine compound constituting the aqueous polyurethane resin is not particularly limited as long as it can bond with an acid group and improve the oxygen barrier property, and various compounds having two or more basic nitrogen atoms are used. The basic nitrogen atom is a nitrogen atom that can bond with the acid group of the acid group-containing polyurethane resin, and examples thereof include nitrogen atoms in amino groups such as primary amino groups, secondary amino groups, and tertiary amino groups. The bond between the polyamine compound and the acid group of the polyurethane resin may be an ionic bond (e.g., an ionic bond between a tertiary amino group and a carboxyl group) or a covalent bond (e.g., an amide bond). The polyamine compound is preferably a polyamine compound having at least one type of amino group selected from the group consisting of a primary amino group, a secondary amino group, and a tertiary amino group.

[0055] Specific examples of polyamine compounds include alkylenediamines, polyalkylenepolyamines, etc. Examples of alkylenediamines include C2 to C10 alkylenediamines such as ethylenediamine, 1,2-propylenediamine, 1,3-propylenediamine, 1,4-butanediamine, and 1,6-hexamethylenediamine. Here, C means the number of carbon atoms. Examples of polyalkylene polyamines include tetraalkylene polyamines and silicon compounds having two or more basic nitrogen atoms (silane coupling agents, etc.). Examples of the silicon compounds include 2-(N-(2-aminoethyl)amino)ethyltrimethoxysilane, 3-(N-(2-aminoethyl)amino)propyltriethoxysilane, etc.

[0056] The amine value of the polyamine compound is preferably 100 to 1900 mgKOH / g, more preferably 150 to 1900 mgKOH / g, even more preferably 200 to 1900 mgKOH / g, particularly preferably 200 to 1700 mgKOH / g, and most preferably 300 to 1500 mgKOH / g. If the amine value of the polyamine compound is 100 mgKOH / g or more, the gas barrier property of the aqueous polyurethane resin is more excellent. If the amine value of the polyamine compound is 1900 mgKOH / g or less, the water dispersion stability of the aqueous polyurethane resin is more excellent.

[0057] The amine value of the polyamine compound is measured by the following method. "Method for measuring amine value" Weigh out 0.5 to 2 g of sample (sample weight Sg). Add 30 g of ethanol to the weighed sample and dissolve it. Add bromophenol blue as an indicator to the resulting solution and titrate with 0.2 mol / L ethanolic hydrochloric acid solution (titer f). The point at which the color of the solution changes from green to yellow is set as the endpoint, and the titer (AmL) at this point is used to calculate the amine value using the following formula. Calculation formula: Amine value (mgKOH / g) = A x f x 0.2 x 56.108 / S

[0058] In the aqueous polyurethane resin, the content of the polyamine compound is preferably such that the molar ratio of the acid groups of the acid group-containing polyurethane resin to the basic nitrogen atoms of the polyamine compound (acid groups / basic nitrogen atoms) is 10 / 1 to 0.1 / 1, and more preferably 5 / 1 to 0.2 / 1. If the acid group / basic nitrogen atom ratio is 10 / 1 to 0.1 / 1, the crosslinking reaction between the acid groups of the acid group-containing polyurethane and the polyamine compound occurs appropriately, and the film formed from the coating agent can exhibit excellent oxygen barrier properties even in a high humidity atmosphere.

[0059] The aqueous polyurethane resin is usually formed in a state of being dissolved or dispersed in an aqueous medium. The aqueous medium is as described above. The aqueous polyurethane resin may be in the form of an aqueous solution in which the polyurethane resin is dissolved in an aqueous medium, or in the form of an aqueous dispersion in which the polyurethane resin is dispersed in an aqueous medium.

[0060] In the aqueous dispersion, the average particle size of the dispersed particles (polyurethane resin particles) is not particularly limited, and is preferably 20 to 500 nm, more preferably 25 to 300 nm, and even more preferably 30 to 200 nm. If the average particle size of the dispersed particles is 500 nm or less, the uniform dispersion of the dispersed particles and other materials and the dispersion stability of the coating agent are good, and the oxygen barrier property of the film formed from the coating agent is more excellent. If the average particle size of the dispersed particles is 20 nm or more, it is easy to obtain an aqueous dispersion. The average particle size is a value measured using a concentrated particle size analyzer (FPAR-10 manufactured by Otsuka Electronics Co., Ltd.) in a state in which water is used as a dispersion medium and the solid content concentration is 0.03 to 0.3 mass %.

[0061] The aqueous polyurethane resin may be a commercially available product or may be produced by a known production method. The production method of the aqueous polyurethane resin is not particularly limited, and ordinary techniques for making polyurethane resin aqueous, such as the acetone method and the prepolymer method, can be applied. In the urethanization reaction, a urethanization catalyst, such as an amine catalyst, a tin catalyst, or a lead catalyst, may be used as necessary. For example, in an inert organic solvent such as ketones such as acetone, ethers such as tetrahydrofuran, or nitriles such as acetonitrile, a polyisocyanate compound, a polyhydroxy acid, and, if necessary, at least one of a polyol component and a chain extender component are reacted to prepare an acid group-containing polyurethane resin. More specifically, in an inert organic solvent (particularly, a hydrophilic or water-soluble organic solvent), a polyisocyanate compound, a polyhydroxy acid, and a polyol component are reacted to generate a prepolymer having an isocyanate group at the end, which is neutralized with a neutralizing agent and dissolved or dispersed in an aqueous medium, and then a chain extender component is added and reacted, and the organic solvent is removed to prepare an aqueous solution or water dispersion of an acid group-containing polyurethane resin. A polyamine compound is added to the aqueous solution or water dispersion of an acid group-containing polyurethane resin thus obtained, and the aqueous polyurethane resin in the form of an aqueous solution or water dispersion can be prepared by heating as necessary. When heating, the heating temperature is preferably 30 to 60°C.

[0062] <Hardening agent> The curing agent is reactive with the components in the coating agent (water-soluble polymers, inorganic layered minerals, water-based polyurethane resins, etc.). By including a curing agent in the coating agent, the adhesion between the coating film made of the coating agent and the resin substrate 1 can be made stronger.

[0063] The type of curing agent is not particularly limited as long as it is reactive with the components in the coating agent. The curing agent is preferably a silane coupling agent or an epoxy compound.

[0064] As the silane coupling agent, any commonly used agent can be used, and examples thereof include compounds having an alkoxy group and an organic reactive group bonded to a silicon atom. The alkoxy group of the silane coupling agent is hydrolyzed to generate a silanol group, which exerts an interactive effect such as reaction with an inorganic compound and adsorption. In the coating agent, the inorganic layered mineral and the silane coupling agent interact with each other to improve the cohesive strength of the film formed from the coating agent. In addition, the organic reactive group of the silane coupling agent reacts with organic components such as water-soluble polymers and aqueous polyurethane resins to improve the adhesive strength of the film formed from the coating agent to the resin substrate 1. Therefore, by including a silane coupling agent in the coating agent, it is possible to increase the cohesive strength of the film formed from the coating agent, improve the adhesiveness to the resin substrate 1 and other substrates, and increase the practical strength as a packaging material.

[0065] Examples of the silane coupling agent include compounds represented by RSiX3 (where R is an organic reactive group and X is an alkoxy group). Examples of the organic reactive group include those having an amino group, a (meth)acrylic group, an epoxy group, a vinyl group, a mercapto group, an isocyanate group, an isocyanurate group, and the like. The (meth)acrylic group refers to both an acrylic group and a methacrylic group. Examples of the alkoxy group include a methoxy group, an ethoxy group, and the like.

[0066] Silane coupling agents having an organic reactive group reactive with the components in the coating agent are preferred. For example, silane coupling agents having a vinyl group include vinyltrimethoxysilane, vinyltriethoxysilane, etc. Silane coupling agents having an epoxy group include 2(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylethyldiethoxysilane, etc. Silane coupling agents having an amino group include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2(aminoethyl)-3-aminopropyltrimethoxysilane, N-2(aminoethyl)-3-aminopropylmethyldimethoxysilane, etc. Silane coupling agents having a mercapto group include 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, etc. Examples of silane coupling agents having a (meth)acrylic group include 3-acryloxypropyltrimethoxysilane. Examples of silane coupling agents having an isocyanate group include 3-isocyanatepropyltriethoxysilane. Examples of silane coupling agents having an isocyanurate group include tris-(trimethoxysilylpropyl)isocyanurate. These silane coupling agents may be used alone or in combination of two or more.

[0067] The silane coupling agent is preferably one having an epoxy group, which has good reactivity with the hydroxyl groups of the aqueous polyurethane resin and the water-soluble polymer, and therefore the film formed from the coating agent exhibits particularly strong adhesion strength to the resin substrate 1.

[0068] The epoxy compound is not particularly limited as long as it has an epoxy group. The epoxy compound reacts with the terminal hydroxyl groups of the aqueous polyurethane resin to form a strong bond. Therefore, by including the epoxy compound in the coating agent, it is possible to increase the cohesive strength of the film, improve the adhesion to the resin substrate 1 and other substrates, and increase the practical strength as a packaging material. In addition, since the reaction rate is within an appropriate range, the usable period after adding the curing agent is long.

[0069] The epoxy compound may be a monofunctional epoxy compound having one epoxy group, or a polyfunctional epoxy compound having two or more epoxy groups, or a combination of these. Examples of monofunctional epoxy compounds include silane coupling agents having an epoxy group, such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and 3-glycidoxypropylethyldiethoxysilane. Examples of monofunctional epoxy compounds other than silane coupling agents having an epoxy group include phenyl glycidyl ether, 2-ethylhexyl glycidyl ether, ethyl diethylene glycol glycidyl ether, dicyclopentadiene glycidyl ether, and 2-hydroxyethyl glycidyl ether. These monofunctional epoxy compounds may be used alone or in combination of two or more.

[0070] Examples of polyfunctional epoxy compounds include hydroquinone diglycidyl ether, resorcinol diglycidyl ether, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, cyclohexene diol diglycidyl ether, cyclohexane dimethanol diglycidyl ether, dicyclopentadiene diol diglycidyl ether, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol tetraglycidyl ether, phenol novolac type epoxy resin, cresol novolac type epoxy resin, epoxidized polybutadiene, etc. Any one of these polyfunctional epoxy compounds may be used alone, or two or more may be used in combination.

[0071] As the epoxy compound, a silane coupling agent having an epoxy group or a polyfunctional epoxy compound is preferred because it can form a complex and strong crosslinked structure. As the polyfunctional epoxy compound, a tri- or higher functional epoxy compound is preferred since it is possible to form a more complicated crosslinked structure.

[0072] <Content of each ingredient> The content (solid content) of the water-soluble polymer in the coating agent is preferably 25 to 80 mass %, more preferably 30 to 75 mass %, and particularly preferably 35 to 70 mass %, based on the total solid content in the coating agent. If the content of the water-soluble polymer is 25 to 80 mass %, the film formed from the coating agent can effectively exhibit barrier properties in a high humidity environment while maintaining the cohesive strength.

[0073] The content (solid content) of the inorganic layered mineral in the coating agent is preferably 5 to 60 mass %, more preferably 7 to 45 mass %, and particularly preferably 10 to 30 mass %, based on the total solid content in the coating agent. If the content of the inorganic layered mineral is 5 to 60 mass %, the film formed from the coating agent can effectively exhibit barrier properties in a high humidity environment while maintaining the cohesive strength.

[0074] When the coating agent contains an aqueous polyurethane resin, the mass ratio of the aqueous polyurethane resin and the water-soluble polymer in the coating agent in terms of solid content (aqueous polyurethane resin / water-soluble polymer) is preferably 5 / 95 to 85 / 15, more preferably 10 / 90 to 75 / 25, and particularly preferably 15 / 85 to 70 / 30. If the aqueous polyurethane resin / water-soluble polymer is 85 / 15 or less, unevenness is unlikely to occur during coating. Unevenness during coating can lead to poor appearance and reduced barrier properties. If the aqueous polyurethane resin / water-soluble polymer is 5 / 95 or more, the wettability to the resin substrate 1 is good, and repelling unevenness is unlikely to occur during coating. Repelling unevenness may lead to reduced oxygen barrier properties. If the aqueous polyurethane resin / water-soluble polymer is 5 / 95 to 85 / 15, the wettability of the coating agent to the resin substrate 1 is good, the coating agent can be applied without unevenness, and a film with good appearance and barrier properties can be formed.

[0075] When the coating agent contains a curing agent, the content (solid content) of the curing agent in the coating agent is preferably 0.5 to 30 mass %, more preferably 1 to 25 mass %, and particularly preferably 3 to 20 mass %, based on the total solid content in the coating agent. If the content of the curing agent is 0.5 to 30 mass %, it is possible to sufficiently increase the cohesive force of the film formed from the coating agent and the adhesive strength to the resin substrate while maintaining good wettability to the resin substrate 1.

[0076] In the coating agent, the total content of the water-soluble polymer, the inorganic layered mineral, the aqueous polyurethane resin, and the curing agent is preferably 85% by mass or more, more preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on the total solid content in the coating agent. The upper limit of this total content is not particularly limited, and may be 100% by mass.

[0077] The viscosity of the coating agent at 23° C. is preferably from 10 to 80 mPa·s, and more preferably from 10 to 50 mPa·s. The viscosity of the coating agent is a value measured by an E-type viscometer.

[0078] The coating agent of this embodiment can be prepared by mixing a water-soluble polymer, an inorganic layered mineral, an aqueous polyurethane resin if necessary, a curing agent if necessary, other components if necessary, and an additional aqueous medium if necessary. The order of mixing the components is not particularly limited. The curing agent may be mixed together with the other components, or may be added immediately before application to the resin substrate 1.

[0079] (Action and effect) The gas barrier film 10 described above includes a resin substrate 1 having a surface layer 2, a back layer 3, and a base layer 4, and a coating 5 located in contact with a first surface 1a of the resin substrate 1. Since the surface layer 2 does not contain an AB agent, the coating 5 does not have defects even if it is thin. As a result, the coating 5 can fully exhibit its inherent oxygen barrier properties and has excellent oxygen barrier properties. In addition, since the thickness of the coating 5 can be made thin, the gas barrier film 10 can be provided at low cost. In addition, in this embodiment, since the back layer 3 contains an AB agent, blocking of the resin substrate 1 and the gas barrier film 10 can be suppressed.

[0080] The reason why the inherent oxygen barrier properties can be sufficiently exhibited even if the film 5 is thin is believed to be as follows. Resin substrates containing AB agents to prevent blocking have convex portions on their surfaces. When a coating agent is applied to such a resin substrate by wet coating, particularly when the amount of coating is small, the coating film is not formed locally at the positions of the convex portions, resulting in defects. It is believed that these defects become paths for gas permeation, and the oxygen barrier properties are not fully expressed. In the gas barrier film 10, since the surface layer 2 does not contain an AB agent, no protrusions due to the AB agent are present on the first surface 1a, and defects in the coating 5 due to the protrusions can be suppressed. Therefore, it is believed that the inherent oxygen barrier property is fully exhibited.

[0081] The configurations and combinations thereof in the present embodiment are merely examples, and additions, omissions, substitutions, and other modifications of the configurations are possible without departing from the spirit of the present invention. For example, the back layer 3 does not have to contain the AB agent 6. From the viewpoints of the production of the resin substrate 1 and the handling of the gas barrier film 10, it is preferable that the back layer 3 contains the AB agent 6. The gas barrier film may further have a printing layer, an anchor coat layer, an overcoat layer, a light-shielding layer, an adhesive layer, a heat-sealable heat-fusible layer, other functional layers, etc., as necessary. When the gas barrier film has a heat-sealable heat-sealable layer, the heat-sealable layer is disposed on at least one outermost surface of the gas barrier film. By having the gas barrier film have a heat-sealable layer, the gas barrier film can be sealed by heat sealing. The thermal adhesion layer can be laminated, for example, on a laminate having a coating 5 provided on the first surface 1a of the resin substrate 1 by a known dry lamination method, extrusion lamination method, etc., using a known adhesive such as a polyurethane-based, polyester-based, or polyether-based adhesive. The thermal adhesion layer may be laminated on the second surface 1b of the resin substrate 1 or on the coating 5.

[0082] A second embodiment of the present invention will now be described. Fig. 2 is a schematic cross-sectional view of a gas barrier film 200 according to the second embodiment of the present invention. The gas barrier film 200 has a resin substrate 20, an underlayer 27, an inorganic oxide layer 28, and a coating 25 (oxygen barrier coating). Either the underlayer 27 or the inorganic oxide layer 28 may be omitted. The underlayer 27 is positioned in contact with the first surface 20a of the resin substrate 20, and the inorganic oxide layer 28 or coating 25 is positioned in contact with the opposite surface. The inorganic oxide layer 28 is located in contact with the first surface 20a of the resin substrate 20 or the underlayer 27, and the coating 25 is located in contact with the opposite surface.

[0083] (Resin substrate) The resin substrate 20 has two or more resin layers including a base layer 24. Specifically, the resin substrate 20 has the base layer 24, a front layer 22 located on one side of the base layer 24, and a back layer 23 located on the other side of the base layer 24. The surface layer 22 constitutes a first surface 20 a of the resin base material 20 . The back layer 23 constitutes a second surface 20b of the resin substrate 20 opposite to the first surface 20a. The resin substrate 20 contains a resin, and each of the layers constituting the resin substrate 20, that is, the front layer 22, the back layer 23, and the base layer 24, also contains a resin.

[0084] The base layer 24 adjusts the mechanical properties, chemical properties, thermal properties, optical properties, etc. of the resin substrate 20. Mechanical properties include rigidity, elongation, stiffness, tear strength, impact strength, puncture strength, pinhole resistance, etc. Chemical properties include water vapor barrier properties, gas barrier properties, aroma retention, chemical resistance, oil resistance, etc. Thermal properties include melting point, glass transition point, heat resistance, cold resistance, thermal shrinkage rate, etc. Optical properties include transparency, gloss, etc.

[0085] From the viewpoints of ease of availability and water vapor barrier properties, a polyolefin-based resin is preferable as the resin used as the raw material for the base layer 24. That is, the resin substrate 20 is preferably a polyolefin-based resin substrate. Examples of polyolefin resins include polyethylene and polypropylene. Polypropylene may be a homopolymer, a random copolymer, or a block copolymer. A homopolymer is a polypropylene consisting of only propylene alone. A random copolymer is a polypropylene in which the main monomer propylene and a different type of comonomer are randomly copolymerized to form a homogeneous phase. A block copolymer is a polypropylene in which the main monomer propylene and the above comonomer are copolymerized in blocks or polymerized in a rubber-like form to form a heterogeneous phase. Any one of these polyolefin resins may be used alone, or two or more may be blended together.

[0086] The base layer 24 may also include additives. The additives can be appropriately selected from various known additives. Examples of the additives include antiblocking agents (AB agents), heat stabilizers, weather stabilizers, ultraviolet absorbers, lubricants, slipping agents, nucleating agents, antistatic agents, antifogging agents, pigments, and dyes. Any one of these additives may be used alone, or two or more may be used in combination. Among the above, lubricants and slipping agents are preferred from the viewpoint of suitability for processing. The content of the additive in the base layer 24 can be appropriately adjusted within a range that does not impair the effects of the present invention. The base layer 24 is typically free of AB agents.

[0087] The base layer 24 may be a single layer or a multi-layer structure. The thickness of the base layer 24 may be, for example, 3 to 200 μm, or 6 to 30 μm.

[0088] The resin constituting the surface layer 22 may be the same as or different from the resin constituting the base layer 24. For example, when the resins constituting each of the surface layer 22 and the base layer 24 are polyolefin-based resins, the polyolefin-based resin constituting the surface layer 22 may be a polyolefin-based resin having a lower melting point than the polyolefin-based resin constituting the base layer 24. This is to improve the adhesion between the resin substrate 20 and the film 25. Examples of polyolefin-based resins that can be used for the surface layer 22 include ethylene-1-butene copolymers, ethylene-propylene-1-butene copolymers, ethylene-acrylic acid copolymers, ionomers obtained by crosslinking ethylene-acrylic acid copolymers with metal ions, polypropylene, poly(1-butene), 1-butene-ethylene copolymers, propylene-ethylene copolymers, propylene-1-butene copolymers, and propylene-pentene copolymers. Any one of these resins may be used alone, or two or more may be blended together.

[0089] The surface layer 22 does not contain an AB agent. Since the surface layer 22 does not contain the AB agent, there are no protrusions resulting from the AB agent on the first surface 20a of the resin substrate 20. Therefore, when the coating 25 is formed by the wet coating method, the occurrence of defects that serve as paths for gas permeation can be suppressed, and excellent oxygen barrier properties are exhibited.

[0090] The surface layer 22 may contain an additive other than the AB agent. The additives can be appropriately selected from various known additives. Examples of the additives include heat stabilizers, weather stabilizers, ultraviolet absorbers, lubricants, slipping agents, nucleating agents, antistatic agents, antifogging agents, pigments, and dyes. Any one of these additives may be used alone, or two or more may be used in combination. Among the above, lubricants and slipping agents are preferred from the viewpoint of processing suitability. The content of the additive in the surface layer 22 can be appropriately adjusted within a range that does not impair the effects of the present invention.

[0091] The thickness of the surface layer 22 may be, for example, 0.1 to 10 μm, or may be 0.5 to 5.0 μm.

[0092] The resin constituting the back layer 23 may be the same as or different from the resin constituting the base layer 24, similar to the resin constituting the surface layer 22. For example, when the resins constituting each of the back layer 23 and the base layer 24 are polyolefin-based resins, the polyolefin-based resin constituting the back layer 23 may be a polyolefin-based resin having a lower melting point than the polyolefin-based resin constituting the base layer 24. Examples of polyolefin-based resins that can be used for the back layer 23 include those listed as polyolefin-based resins that can be used for the surface layer 22.

[0093] 1, the backing layer 23 contains an AB agent 26. The AB agent 26 is dispersed in the backing layer 23. Since the back layer 23 contains the AB agent 26, protrusions resulting from the AB agent 26 are locally present on the second surface 20b of the resin substrate 20. These protrusions can suppress blocking of the resin substrate 20 and the gas barrier film 200. On the second surface 20b, the AB agent 26 may be exposed or may be covered with a resin.

[0094] The AB agent 26 is a solid particle, and examples thereof include organic particles and inorganic particles. Examples of organic particles include polymethyl methacrylate particles, polystyrene particles, and polyamide particles. These organic particles are obtained, for example, by emulsion polymerization or suspension polymerization. Examples of inorganic particles include silica particles, zeolite, talc, kaolinite, and feldspar. These AB agents may be used alone or in combination of two or more. As the AB agent 26, polymethyl methacrylate particles are preferred for the organic system, and silica particles are preferred for the inorganic system.

[0095] The average particle size of the AB agent 26 is typically equal to or less than the thickness of the back layer 23. In consideration of the appearance of the second surface 20b, the transparency of the back layer 23, the possibility of the AB agent 26 falling off, and the anti-blocking performance, the average particle size of the AB agent 26 is preferably 0.1 μm or more and 5 μm or less. In the gas barrier film 200, the front layer 22 does not contain the AB agent 26. Therefore, it is preferable that the anti-blocking performance of the AB agent 26 in the back layer 23 is high. From the viewpoint of anti-blocking performance, it is particularly preferable that the average particle size of the AB agent 26 is 2 μm or more and 5 μm or less. The average particle size of the AB agent 26 is measured by the Coulter method.

[0096] The amount of the AB agent 26 added to the back layer 23 is, for example, 0.1 to 0.4 mass % relative to the total mass of the back layer 23. The amount of the AB agent 26 added to the back layer 13 is specifically calculated by the following formula. Amount of AB agent added [mass%] = {(i) / 100} × {(ii) / 100} × 100 In the formula, (i) indicates the concentration (mass %) of the AB agent in the masterbatch resin chips obtained by adding the AB agent to a resin, stirring the mixture, feeding the mixture into an extruder and kneading the mixture, and forming the mixture into pellets by melt extrusion. (ii) indicates the concentration (mass %) of masterbatch resin chips containing an AB agent relative to the total mass of the resin pellets constituting the back layer 23 when the masterbatch resin chips containing an AB agent are blended with a resin not containing an AB agent.

[0097] The back layer 23 may contain additives other than the AB agent. Examples of additives include the same additives as those described above. The content of the additives in the back layer 23 can be appropriately adjusted within a range that does not impair the effects of the present invention.

[0098] The thickness of the back layer 23 may be, for example, 0.1 to 10 μm, or may further be 0.5 to 5.0 μm. The thickness of the back layer 23 is the thickness of a portion where the protrusions resulting from the AB agent 26 are not present.

[0099] The resin substrate 20 is preferably a coextruded film in which a front layer 22, a back layer 23, and a base layer 24 are laminated by coextrusion. The resin substrate 20 may be a stretched film or an unstretched film.

[0100] The resin substrate 20 preferably has a biaxially oriented polypropylene film. Since a biaxially oriented polypropylene film has particularly excellent water vapor barrier properties, the gas barrier film 200 has improved water vapor barrier properties by having the biaxially oriented polypropylene film. The biaxially oriented polypropylene film may be at least one of a homopolymer, a random copolymer, a block copolymer, etc., processed into a film shape. The biaxially oriented polypropylene film is preferably a coextruded film.

[0101] The resin substrate having the biaxially oriented polyolefin film may be made of a biaxially oriented polypropylene film, or may be a laminate of a biaxially oriented polypropylene film and another resin film. Examples of the other resin film include polyester films such as polyethylene terephthalate and polyethylene naphthalate, polyolefin resin films such as polyethylene, polystyrene films, polyamide films such as nylon, polycarbonate films, polyacrylonitrile films, and engineering plastic films such as polyimide films.

[0102] The thickness of the resin base material 20 can be adjusted depending on the application, the desired properties, etc., and is not particularly limited, but may be, for example, 3 to 200 μm, or may further be 6 to 30 μm. The thickness of the resin substrate 20 is the thickness of a portion where no protrusions resulting from the AB agent 26 exist.

[0103] The surfaces (first surface 20a, second surface 20b) of the resin substrate 20 may be subjected to at least one treatment selected from the group consisting of chemical treatment, solvent treatment, corona treatment, plasma treatment, and ozone treatment.

[0104] (base layer) The underlayer 27 is provided between the resin substrate 20 and the inorganic oxide layer 28 or the oxygen barrier film 25 . The underlayer 27 is a layer containing an organic polymer as a main component, and is sometimes called a primer layer. By providing the underlayer 27, the film-forming property and adhesive strength of the inorganic oxide layer 28 or the coating 25 can be improved.

[0105] The content of the organic polymer in the underlayer 27 may be, for example, 70% by mass or more, or 80% by mass or more. Examples of the organic polymer include polyacrylic resin, polyester resin, polycarbonate resin, polyurethane resin, polyamide resin, polyolefin resin, polyimide resin, melamine resin, and phenol resin. Considering the hot water resistance of the adhesive strength between the resin substrate 20 and the inorganic oxide layer 28 or the coating 25, it is preferable that the underlayer 27 contains at least one of a polyacrylic resin, a polyol resin, a polyurethane resin, a polyamide resin, or a reaction product of these organic polymers. The underlayer 27 may also contain a silane coupling agent, an organic titanate, or a modified silicone oil.

[0106] More preferred examples of the organic polymer include an organic polymer having a urethane bond produced by the reaction of a polyol having two or more hydroxyl groups at the polymer terminal with an isocyanate compound, and / or an organic polymer containing a reaction product of a polyol having two or more hydroxyl groups at the polymer terminal with an organic silane compound such as a silane coupling agent or a hydrolyzate thereof.

[0107] Examples of polyols include at least one selected from acrylic polyol, polyvinyl acetal, polystyrene polyol, and polyurethane polyol. The acrylic polyol may be obtained by polymerizing an acrylic acid derivative monomer, or may be obtained by copolymerizing an acrylic acid derivative monomer with another monomer. Examples of the acrylic acid derivative monomer include ethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxybutyl methacrylate. Examples of the monomer to be copolymerized with the acrylic acid derivative monomer include styrene.

[0108] The isocyanate compound has the effect of increasing the adhesion between the resin substrate 20 and the inorganic oxide layer 28 or the coating 25 by forming a urethane bond by reacting with the polyol. That is, the isocyanate compound functions as a crosslinking agent or a curing agent. Examples of the isocyanate compound include aromatic tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), aliphatic xylene diisocyanate (XDI), hexamethylene diisocyanate (HMDI), and isophorone diisocyanate (IPDI) monomers, polymers thereof, and derivatives thereof. The above-mentioned isocyanate compounds may be used alone or in combination of two or more.

[0109] Examples of silane coupling agents include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane. The organic silane compound may be a hydrolyzate of these silane coupling agents. The organic silane compound may contain one of the above-mentioned silane coupling agents and their hydrolyzates alone, or two or more of them in combination.

[0110] The underlayer 27 can be formed by preparing a mixed solution by mixing the above-mentioned components in an organic solvent at any ratio, and using the mixed solution prepared on the first surface a of the resin substrate 20. The mixed solution may contain, for example, a curing accelerator, an antioxidant, a leveling agent, a flow control agent, a catalyst, a crosslinking reaction accelerator, a filler, and the like. Examples of the curing accelerator include tertiary amines, imidazole derivatives, metal salt compounds of carboxylic acids, quaternary ammonium salts, and quaternary phosphonium salts. Examples of the antioxidant include phenols, sulfurs, and phosphites.

[0111] The mixed liquid can be coated on the resin substrate 20 by using a known printing method such as offset printing, gravure printing, or silk screen printing, or a known application method such as roll coating, knife edge coating, or gravure coating. After coating, the mixture can be heated to, for example, 50 to 200° C., and dried and / or cured to form the undercoat layer 27.

[0112] The thickness of the underlayer 27 is not particularly limited and may be, for example, 0.005 to 5 μm. The thickness may be adjusted depending on the application or the desired characteristics. The thickness of the underlayer 27 is preferably 0.01 to 1 μm, and more preferably 0.01 to 0.5 μm. If the thickness of the underlayer 27 is 0.01 μm or more, sufficient adhesive strength between the resin substrate 20 and the inorganic oxide layer 28 or the coating 25 is obtained, and the oxygen barrier property is also good. If the thickness of the underlayer 27 is 1 μm or less, it is easy to form a uniform coating surface, and the drying load and manufacturing costs can be suppressed.

[0113] (Inorganic oxide layer) Examples of materials constituting the inorganic oxide layer 28 include aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, tin oxide, zinc oxide, and indium oxide. In particular, aluminum oxide or silicon oxide is preferred because it has excellent productivity and excellent oxygen barrier properties and water vapor barrier properties in heat resistance and moist heat resistance. The inorganic oxide layer 28 may contain one of these materials alone or two or more of them in combination. The thickness of the inorganic oxide layer 28 is preferably 1 to 200 nm. If the thickness is 1 nm or more, excellent oxygen barrier property and water vapor barrier property can be obtained, and if the thickness is 200 nm or less, the manufacturing cost can be kept low, cracks due to external forces such as bending and pulling are unlikely to occur, and deterioration of the barrier property can be suppressed. The inorganic oxide layer 28 can be formed by a known film formation method such as vacuum deposition, sputtering, ion plating, or plasma chemical vapor deposition (CVD).

[0114] (Oxygen barrier film) The film 25 may be a known oxygen barrier film formed by a wet coating method. The film 25 is obtained by forming a coating film made of a coating agent on the underlayer 27 or the inorganic oxide layer 28 by a wet coating method and drying the coating film. The coating film is a wet film, and the film is a dry film.

[0115] The coating 25 is preferably a coating (organic-inorganic composite coating) containing at least one of a metal alkoxide and its hydrolysate or a reaction product thereof and a water-soluble polymer, and more preferably a coating further containing at least one of a silane coupling agent and its hydrolysate.

[0116] Examples of metal alkoxides and their hydrolysates contained in the organic-inorganic composite film include those represented by the general formula M(OR), such as tetraethoxysilane [Si(OC2H5)4] and triisopropoxyaluminum [Al(OC3H7)3]. n and hydrolysates thereof. One of these may be contained alone, or two or more of them may be contained in combination.

[0117] The total content of at least one of the metal alkoxide and its hydrolysate and / or its reaction product in the organic-inorganic composite membrane is, for example, 40 to 70 mass%. From the viewpoint of further reducing oxygen permeability, the lower limit of the total content of at least one of the metal alkoxide and its hydrolysate and / or its reaction product in the organic-inorganic composite membrane may be 50 mass%. From the same viewpoint, the upper limit of the total content of at least one of the metal alkoxide and its hydrolysate and / or its reaction product in the organic-inorganic composite membrane may be 65 mass%.

[0118] The water-soluble polymer contained in the organic-inorganic composite film is not particularly limited, and examples thereof include polyvinyl alcohol-based polymers, polysaccharides such as starch, methyl cellulose, and carboxymethyl cellulose, and acrylic polyol-based polymers. From the viewpoint of further improving the oxygen gas barrier property, the water-soluble polymer preferably contains a polyvinyl alcohol-based polymer. The number average molecular weight of the water-soluble polymer is, for example, 40,000 to 180,000.

[0119] A water-soluble polymer such as polyvinyl alcohol can be obtained by, for example, saponifying polyvinyl acetate (including partial saponification). This water-soluble polymer may have several tens of percent of acetate groups remaining, or may have only a few percent of acetate groups remaining.

[0120] The content of the water-soluble polymer in the organic-inorganic composite film is, for example, 15 to 50 mass%. The lower limit of the content of the water-soluble polymer in the organic-inorganic composite film may be 20 mass% from the viewpoint of further reducing oxygen permeability. The upper limit of the content of the water-soluble polymer in the organic-inorganic composite film may be 45 mass% from the viewpoint of further reducing oxygen permeability.

[0121] The silane coupling agent and its hydrolysate contained in the organic-inorganic composite film include silane coupling agents having organic functional groups. Such silane coupling agents and their hydrolysates include ethyltrimethoxysilane, vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, and their hydrolysates. One of these may be contained alone, or two or more may be contained in combination.

[0122] At least one of the silane coupling agent and its hydrolysate is preferably one having an epoxy group as an organic functional group. Examples of the silane coupling agent having an epoxy group include γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. The silane coupling agent having an epoxy group and its hydrolysate may have an organic functional group other than the epoxy group, such as a vinyl group, an amino group, a methacryl group, or a ureyl group.

[0123] A silane coupling agent having an organic functional group and its hydrolysate can further improve the oxygen barrier property of the coating 25 and the adhesion to the underlayer 27 or the inorganic oxide layer 28 due to the interaction between the organic functional group and the hydroxyl group of the water-soluble polymer. In particular, the epoxy group of the silane coupling agent and its hydrolysate can form a coating 25 that is particularly excellent in oxygen barrier property and adhesion to the underlayer 27 or the inorganic oxide layer 28 due to the interaction between the hydroxyl group of the polyvinyl alcohol.

[0124] The total content of at least one of the silane coupling agent and its hydrolysate and / or its reaction product in the organic-inorganic composite film is, for example, 1 to 15 mass%. From the viewpoint of further reducing oxygen permeability, the lower limit of the total content of at least one of the silane coupling agent and its hydrolysate and / or its reaction product in the organic-inorganic composite film may be 2 mass%. From the same viewpoint, the upper limit of the total content of at least one of the silane coupling agent and its hydrolysate and / or its reaction product in the organic-inorganic composite film may be 12 mass%.

[0125] The organic-inorganic composite film may contain a crystalline inorganic layered compound having a layered structure. Examples of the inorganic layered compound include clay minerals such as kaolinite, smectite, and mica. These may be used alone or in combination of two or more. The particle size of the inorganic layered compound is, for example, 0.1 to 10 μm. The aspect ratio of the inorganic layered compound is, for example, 50 to 5000.

[0126] As the inorganic layered compound, a clay mineral of the smectite group is preferable because a water-soluble polymer can be inserted between the layers of the layered structure (intercalation) to form a film having excellent oxygen barrier properties and adhesive strength. Specific examples of the clay mineral of the smectite group include montmorillonite, hectorite, saponite, water-swellable synthetic mica, etc.

[0127] Another preferred example of the oxygen barrier film 25 is a film containing a polyvalent metal salt of carboxylic acid, which is a reaction product between a carboxy group of a polycarboxylic acid polymer (A) and a polyvalent metal compound (B) (polycarboxylic acid polyvalent metal salt film). In this case, the film may be a polycarboxylic acid polyvalent metal salt film formed by applying a coating agent in which a polycarboxylic acid polymer (A) and a polyvalent metal compound (B) are mixed and then heated and dried, or a polycarboxylic acid polyvalent metal salt film formed by applying a coating agent mainly composed of a polycarboxylic acid polymer (A) and drying to form a film A, applying a coating agent mainly composed of a polyvalent metal compound (B) on the film A, and then drying the coating to form a film B, and then allowing a crosslinking reaction between the A and B layers.

[0128] [Polycarboxylic acid polymer (A)] A polycarboxylic acid polymer is a polymer having two or more carboxy groups in the molecule. Examples of polycarboxylic acid polymers include (co)polymers of ethylenically unsaturated carboxylic acids, copolymers of ethylenically unsaturated carboxylic acids and other ethylenically unsaturated monomers, and acidic polysaccharides having carboxyl groups in the molecule, such as alginic acid, carboxymethylcellulose, and pectin. Examples of the ethylenically unsaturated carboxylic acid include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Examples of ethylenically unsaturated monomers copolymerizable with ethylenically unsaturated carboxylic acids include ethylene, propylene, vinyl esters of saturated carboxylic acids such as vinyl acetate, alkyl acrylates, alkyl methacrylates, alkyl itaconates, vinyl chloride, vinylidene chloride, styrene, acrylamide, and acrylonitrile. These polycarboxylic acid polymers may be used alone or in combination of two or more.

[0129] Among the above, from the viewpoint of the gas barrier properties of the resulting gas barrier film, the component is preferably a polymer containing a structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, itaconic acid, fumaric acid, and crotonic acid. A polymer containing a structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid is particularly preferred. In the above polymer, the proportion of structural units derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid is preferably 80 mol % or more, and more preferably 90 mol % or more (where the total of all structural units constituting the polymer is 100 mol %). The polymer may be a homopolymer or a copolymer. When the polymer is a copolymer containing other structural units than the above structural units, examples of the other structural units include structural units derived from ethylenically unsaturated monomers copolymerizable with the above-mentioned ethylenically unsaturated carboxylic acid.

[0130] The number average molecular weight of the polycarboxylic acid polymer is preferably within the range of 2,000 to 10,000,000, and more preferably 5,000 to 1,000,000. If the number average molecular weight is less than 2,000, the resulting gas barrier film cannot achieve sufficient water resistance, and the gas barrier properties and transparency may deteriorate due to moisture, or whitening may occur. On the other hand, if the number average molecular weight exceeds 10,000,000, the viscosity of the coating agent when forming the film 25 may increase, and the coatability may be impaired. The number average molecular weight is a polystyrene-equivalent number average molecular weight determined by gel permeation chromatography (GPC).

[0131] When a coating agent mainly composed of a polycarboxylic acid polymer (A) is applied and dried to form a coating film A, and then a coating film B is formed, the polycarboxylic acid polymer may have a part of its carboxyl groups neutralized in advance with a basic compound. By neutralizing a part of the carboxyl groups of the polycarboxylic acid polymer in advance, the water resistance and heat resistance of the coating film A can be further improved. The basic compound is preferably at least one basic compound selected from the group consisting of polyvalent metal compounds, monovalent metal compounds, and ammonia. As the polyvalent metal compound, the compounds exemplified in the description of the polyvalent metal compound (B) described below can be used. As the monovalent metal compound, for example, sodium hydroxide, potassium hydroxide, etc. can be mentioned.

[0132] Various additives can be added to the coating agent containing the polycarboxylic acid polymer (A) as the main component. These include crosslinking agents, curing agents, leveling agents, defoamers, antiblocking agents, antistatic agents, dispersants, surfactants, softeners, stabilizers, film-forming agents, thickeners and the like, within the range that does not impair the barrier performance.

[0133] The solvent used in the coating agent containing the polycarboxylic acid polymer (A) as the main component is preferably an aqueous medium. Examples of the aqueous medium include water, water-soluble or hydrophilic organic solvents, and mixtures thereof. The aqueous medium usually contains water or water as the main component. The water content in the aqueous medium is preferably 70% by mass or more, and more preferably 80% by mass or more. Examples of water-soluble or hydrophilic organic solvents include alcohols such as methanol, ethanol, and isopropanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran; cellosolves, carbitols, and nitriles such as acetonitrile.

[0134] [Polyvalent metal compounds (B)] The polyvalent metal compound is not particularly limited as long as it is a compound that reacts with the carboxyl group of the polycarboxylic acid polymer to form a polyvalent metal salt of polycarboxylic acid, and examples thereof include zinc oxide particles, magnesium oxide particles, magnesium methoxide, copper oxide, calcium carbonate, etc. These may be used alone or in combination. Zinc oxide is preferred from the viewpoint of the oxygen barrier properties of the oxygen barrier coating.

[0135] Zinc oxide is an inorganic material having ultraviolet absorbing ability, and the average particle size of the zinc oxide particles is not particularly limited. From the viewpoints of gas barrier property, transparency, and coating suitability, the average particle size of the zinc oxide particles is preferably 5 μm or less, more preferably 1 μm or less, and particularly preferably 0.1 μm or less.

[0136] When a coating agent mainly composed of a polyvalent metal compound (B) is applied and dried to form a B film, various additives may be contained in addition to zinc oxide particles as necessary within the range that does not impair the effects of the present invention. Examples of additives include resins soluble or dispersible in the solvent used in the coating agent, dispersants soluble or dispersible in this solvent, surfactants, softeners, stabilizers, film-forming agents, thickeners, etc.

[0137] Among the above, it is preferable to contain a resin that is soluble or dispersible in the solvent used in the coating agent. This improves the coatability and film-forming properties of the coating agent. Examples of such resins include alkyd resins, melamine resins, acrylic resins, urethane resins, polyester resins, phenolic resins, amino resins, fluorine resins, epoxy resins, and isocyanate resins.

[0138] It is also preferable to contain a dispersant that is soluble or dispersible in the solvent used in the coating agent. This improves the dispersibility of the polyvalent metal compound. As the dispersant, an anionic surfactant or a nonionic surfactant can be used. Examples of these surfactants include (poly)carboxylates, alkyl sulfates, alkylbenzene sulfonates, alkylnaphthalene sulfonates, alkyl sulfosuccinates, alkyl diphenyl ether disulfonates, alkyl phosphates, aromatic phosphates, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, alkyl allyl sulfates, polyoxyethylene alkyl phosphates, sorbitan alkyl esters, glycerin fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyethylene glycol fatty acid esters, polyoxyethylene sorbitan alkyl esters, polyoxyethylene alkyl allyl ethers, polyoxyethylene derivatives, polyoxyethylene sorbitol fatty acid esters, polyoxy fatty acid esters, and polyoxyethylene alkylamines. These surfactants may be used alone or in combination of two or more.

[0139] When an additive is contained in a coating agent mainly composed of a polyvalent metal compound (B), the mass ratio of the polyvalent metal compound to the additive (polyvalent metal compound:additive) is preferably within the range of 30:70 to 99:1, and more preferably within the range of 50:50 to 98:2.

[0140] Examples of the solvent used in the coating agent mainly composed of the polyvalent metal compound (B) include water, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-pentyl alcohol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate. These solvents may be used alone or in combination of two or more. Among these, from the viewpoint of coatability, methyl alcohol, ethyl alcohol, isopropyl alcohol, toluene, ethyl acetate, methyl ethyl ketone, and water are preferred, and from the viewpoint of manufacturability, methyl alcohol, ethyl alcohol, isopropyl alcohol, and water are preferred.

[0141] When a coating agent containing a polycarboxylic acid polymer (A) and a polyvalent metal compound (B) is applied and dried to form a polycarboxylic acid polyvalent metal salt film, the polycarboxylic acid polymer (A) and the polyvalent metal compound (B) are mixed with a resin or dispersant that can be dissolved or dispersed in water or alcohol as a solvent, and additives as necessary, and the mixture is applied and dried by a known coating method to form a polycarboxylic acid polyvalent metal salt film. Examples of the coating method include casting, dipping, roll coating, gravure coating, screen printing, reverse coating, spray coating, kit coating, die coating, metaling bar coating, chamber doctor combined coating, curtain coating, etc.

[0142] The thickness of the oxygen barrier film 25 is set according to the required oxygen barrier properties, and may be, for example, 0.05 to 5 μm. The thickness of the coating 25 is preferably 0.05 to 1 μm, and more preferably 0.1 to 0.5 μm. If the thickness of the coating 25 is 0.05 μm or more, sufficient oxygen barrier properties are easily obtained. If the thickness of the coating 25 is 1 μm or less, the presence or absence of protrusions derived from the AB agent on the first surface 20a has a large effect on the oxygen barrier properties, and the usefulness of the present invention is high. Furthermore, if the thickness of the coating 25 is 1 μm or less, it is easy to form a uniform coated surface, and the drying load and manufacturing costs can be suppressed.

[0143] Gas barrier films having the above-mentioned organic-inorganic composite film or the above-mentioned polyvalent metal salt film of polycarboxylic acid as a gas barrier film maintain excellent oxygen barrier properties even after boiling or retort sterilization. Therefore, when laminated with a sealant film, they have sufficient adhesion and sealing strength to be used as packaging materials for boiling and retort treatments. In addition, they have the advantages of transparency not found in metal foils or metal vapor deposition films, excellent bending and stretching resistance, and no risk of generating harmful substances such as dioxins.

[0144] (Method of manufacturing gas barrier film) The gas barrier film 200 can be produced by forming an underlayer 27, an inorganic oxide layer 28, or both the underlayer 27 and the inorganic oxide layer 28 on the first surface a of the resin substrate 20, and then forming an oxygen barrier coating 25 on the underlayer 27 or the inorganic oxide layer 28. The resin base material 20 may be a commercially available product or may be manufactured by a known method.

[0145] As described above, the undercoat layer 27 is obtained by forming a coating film made of a coating agent on the first surface a of the resin substrate 20 by a wet coating method, and then drying the coating film. As the wet coating method, known wet coating methods such as roll coating, gravure coating, reverse coating, die coating, screen printing, and spray coating can be used. The method for drying the coating film made of the coating agent can be a known drying method such as hot air drying, hot roll drying, infrared irradiation, etc. The drying conditions can be, for example, 90° C. for 10 seconds.

[0146] The inorganic oxide layer 28 is obtained by forming a film on the first surface a of the resin substrate 20 or on the underlayer 27 by the above-mentioned vacuum deposition method, sputtering method, ion plating method, plasma chemical vapor deposition (CVD) method, or the like.

[0147] The oxygen barrier film 25 is obtained by forming a coating film made of the above-mentioned coating agent on the undercoat layer 27 or the inorganic oxide layer 28 by a wet coating method, and then drying the coating film. As the wet coating method, known wet coating methods such as roll coating, gravure coating, reverse coating, die coating, screen printing, and spray coating can be used. The method for drying the coating film made of the coating agent can be a known drying method such as hot air drying, hot roll drying, infrared irradiation, etc. The drying conditions can be, for example, 90° C. for 10 seconds. The oxygen barrier film 25 may be formed by a single coating and drying process, or may be formed by repeatedly coating and drying the same or different coating agents multiple times.

[0148] When convexities caused by the AB agent exist on the surface of the resin substrate, the convexities caused by the AB agent exist on both sides (first and second sides) of the resin substrate. It is believed that defects occur locally in the inorganic oxide layer or oxygen barrier coating at the positions of these convexities, creating paths for gas permeation and preventing sufficient barrier properties from being expressed.

[0149] (Action and effect) In the gas barrier film 200, since the surface layer 22 does not contain an AB agent, no protrusions due to the AB agent are present on the first surface 20a, and defects in the inorganic oxide layer 28 and the coating 25 due to the protrusions can be suppressed. Therefore, it is believed that the inherent barrier properties are fully exhibited. In this embodiment, the back layer 23 contains an AB agent, which can suppress blocking of the resin substrate 20 and the gas barrier film 200. In this case, if the thickness of the base layer 21 is greater than the particle size of the AB agent, the base layer can sufficiently suppress the effect of the AB agent on the unevenness of the surface layer, so that it is possible to simultaneously suppress defects in the inorganic oxide layer 28 and the coating 25 and suppress blocking to a high degree.

[0150] The configurations and combinations thereof in the present embodiment are merely examples, and additions, omissions, substitutions, and other modifications of the configurations are possible without departing from the spirit of the present invention. For example, the back layer 23 does not have to contain the AB agent 26. From the viewpoints of the production of the resin substrate 20 and the handling of the gas barrier film 200, it is preferable that the back layer 23 contains the AB agent 26. The gas barrier film may further have a printing layer, an anchor coat layer, an overcoat layer, a light-shielding layer, an adhesive layer, a heat-sealable heat-fusible layer, other functional layers, etc., as necessary. When the gas barrier film has a heat-sealable heat-sealable layer, the heat-sealable layer is disposed on at least one outermost surface of the gas barrier film. By having the heat-sealable layer, the gas barrier film can be sealed by heat sealing.

[0151] The heat-sealing layer can be laminated by a known dry lamination method, extrusion lamination method, etc. using a known adhesive such as a polyurethane-based, polyester-based, polyether-based, etc. The heat-sealing layer may be laminated on the second surface 20b of the resin substrate 20 or on the coating 25. EXAMPLES

[0152] The present invention will be described in more detail below with reference to examples and comparative examples, although the present invention is not limited to the following examples.

[0153] <Production Example 1> 45.5 g of meta-xylylene diisocyanate (hereinafter sometimes referred to as "mXDI"), 93.9 g of 1,3-bis(isocyanatemethyl)cyclohexane (hereinafter sometimes referred to as "hydrogenated XDI"), 24.8 g of ethylene glycol, 13.4 g of dimethylolpropionic acid, and 80.2 g of methyl ethyl ketone as a solvent were mixed and reacted under a nitrogen atmosphere at 70°C for 5 hours to prepare a carboxyl group-containing urethane prepolymer solution. Next, this carboxyl group-containing urethane prepolymer solution was neutralized with 9.6 g of triethylamine at 40° C. This carboxyl group-containing urethane prepolymer solution was dispersed in 624.8 g of water using a homodisper, and a chain extension reaction was carried out with 21.1 g of 2-[(2-aminoethyl)amino]ethanol. The methyl ethyl ketone was then distilled off to obtain an aqueous dispersion of an acid group-containing polyurethane resin with a solid content of 25% by mass, an average particle size of 90 nm, and an acid value of 26.9 mgKOH / g. Next, this aqueous dispersion of acid group-containing polyurethane resin was mixed with γ-(2-aminoethyl)aminopropylmethyldimethoxysilane (amine value 544 mgKOH / g) as a polyamine compound in a ratio such that the molar ratio of acid groups to basic nitrogen atoms was 1 / 1 to obtain the aqueous polyurethane resin of Production Example 1.

[0154] <Production Example 2> The aqueous polyurethane resin of Production Example 1 was used as the aqueous polyurethane resin containing an acid group-containing polyurethane resin and a polyamine compound (hereinafter also referred to as "component (C)"). As the water-soluble polymer (hereinafter also referred to as "component (D)"), a polyvinyl alcohol resin (product name: Poval PVA-105, manufactured by Kuraray Co., Ltd., polyvinyl alcohol with a saponification degree of 98 to 99% and a polymerization degree of 500) was used. As the inorganic layered mineral (hereinafter, sometimes referred to as "component (E)"), water-swellable synthetic mica (Somasif MEB-3, manufactured by Co-op Chemical Co., Ltd.) was used. Components (C), (D), and (E) were mixed in the solid content ratios shown in Table 1, heated to 80°C, mixed, and then cooled to room temperature. The mixture was diluted with ion-exchanged water and isopropanol so that 10% by mass of the solvent was isopropanol and the final solid content concentration was 9% by mass. A water-soluble polyisocyanate (Takenate WD-725, manufactured by Mitsui Chemicals, Inc.) was added as a curing agent (hereinafter also referred to as "component (F)") to prepare a coating agent. Component (F) was added immediately before application of the coating agents in Examples 1 to 3 and Comparative Examples 1 to 2 described below.

[0155] [Table 1]

[0156] <Example 1> A biaxially oriented polypropylene film A with a thickness of 20 μm was used as the resin substrate. This biaxially oriented polypropylene film A is a co-extruded film with a total of five layers, consisting of one surface layer (thickness 1 μm), three base layers (thickness 18 μm), and one back layer (thickness 1 μm) laminated in this order. Corona treatment was performed only on the first surface (surface on the surface side) of the biaxially oriented polypropylene film A. Silica particles with an average particle size of 4 μm were added to the back layer as an AB agent so that the amount was 2000 ppm relative to the total mass of the back layer. The first surface of this resin substrate was coated with the coating agent of Production Example 2 using a gravure printing machine to form a coating film. This resin substrate was passed through a 90°C oven for 10 seconds to dry the coating film and form a coating film, thereby obtaining the gas barrier film of Example 1.

[0157] <Example 2> The same resin substrate as in Example 1 was used, and the amount of coating agent applied was increased to form a film thicker than that in Example 1, thereby obtaining a gas barrier film of Example 2.

[0158] <Example 3> The gas barrier film of Example 3 was obtained by forming a thinner film than that of Example 1 by reducing the amount of coating agent applied to the same resin substrate as that used in Example 1.

[0159] <Comparative Example 1> A biaxially oriented polypropylene film B with a thickness of 20 μm was used as the resin substrate. This biaxially oriented polypropylene film B is a co-extruded film with a total of five layers, in which one surface layer (thickness 1 μm), three base layers (thickness 18 μm), and one back layer (thickness 1 μm) are laminated in this order. Corona treatment was performed only on the first surface (surface on the surface layer side) of the biaxially oriented polypropylene film B. Polymethyl methacrylate (PMMA) particles with an average particle size of 4 μm were added as an AB agent to the surface layer so that the amount was 1500 ppm with respect to the total mass of the surface layer. Silica particles with an average particle size of 4 μm were added as an AB agent to the back layer so that the amount was 2000 ppm with respect to the total mass of the back layer. The coating agent of Production Example 2 was applied to the first surface of this resin substrate using a gravure printing machine to form a coating film. The resin substrate was passed through an oven at 90° C. for 10 seconds to dry the coating film and form a coating film, thereby obtaining a gas barrier film of Comparative Example 1.

[0160] <Comparative Example 2> The same resin substrate as used in Comparative Example 1 was used, and the amount of coating agent applied was increased to form a film thicker than that in Comparative Example 1, thereby obtaining a gas barrier film of Comparative Example 2.

[0161] <Evaluation> -Oxygen barrier properties The gas barrier films of Examples 1 to 3 and Comparative Examples 1 and 2 were measured for oxygen transmission rate (OTR) (cc / (m) under an atmosphere of 30°C and 60% RH using an oxygen transmission rate measuring device (product name: OXTRAN-2 / 20, manufactured by MOCON). 2 The results are shown in Table 2.

[0162] -Water vapor barrier properties The gas barrier films of Examples 1 to 3 and Comparative Examples 1 and 2 were measured for water vapor transmission rate (WVTR) (g / (m) under an atmosphere of 40°C and 90% RH using a water vapor transmission rate measuring device (product name: PERMATRAN-W-3 / 33, manufactured by MOCON). 2The results are shown in Table 2. · Film thickness The thickness of the film was measured using a scanning electron microscope (product name: JSM6700F, manufactured by JEOL Ltd.) for the gas barrier films of Examples 1 to 3 and Comparative Examples 1 and 2. The results are shown in Table 2.

[0163] [Table 2]

[0164] As shown in Table 2, the gas barrier films of Examples 1 to 3 exhibited good oxygen barrier properties. In particular, Example 1 exhibited oxygen barrier properties equivalent to those of Example 2, despite the film thickness being thinner than that of Example 2. The gas barrier film of Comparative Example 1, which contained an AB agent in the surface layer of the resin substrate, was inferior in oxygen gas barrier property to those of Examples 1 to 3. The gas barrier film of Comparative Example 2 had improved oxygen barrier properties due to the thicker coating than Comparative Example 1, but the oxygen barrier properties were inferior to those of Examples 1 and 2. A cross-sectional photograph of the gas barrier film of Comparative Example 2 taken with a scanning electron microscope (SEM) is shown in Fig. 3. It can be seen that even in the case of a thick coating 5, local cracks occur due to the presence of the AB agent 6 in the surface layer.

[0165] The following examples and comparative examples relate to the second embodiment. <Production Example 3> Acrylic polyol Acrydic CL-1000 (DIC Corporation) was used as the acrylic polyol, and the TDI type curing agent Coronate 2030 (Tosoh Corporation) was used as the isocyanate compound. The acrylic polyol and isocyanate compound were mixed in a solids weight ratio of 6:4, and a dilution solvent (ethyl acetate) was used to prepare mixed solution A (solids content: 2% by mass) for forming the undercoat layer.

[0166] <Production Example 4> An aqueous solution of polyvinyl alcohol resin (PVA, product name: Poval PVA-105, manufactured by Kuraray Co., Ltd., polyvinyl alcohol with a saponification degree of 98-99% and a polymerization degree of 500) was dissolved, and an aqueous solution of tetraethoxysilane (TEOS) and γ-glycidoxypropyltrimethoxysilane (GPTMS, product name: KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) was hydrolyzed with 0.02 mol / L hydrochloric acid. This aqueous solution was mixed so that the weight ratio of PVA:TEOS:GPTMS before hydrolysis was 40:50:10. Isopropyl alcohol was added to this aqueous solution as a diluting solvent, and the solvent components were adjusted to a mass ratio of water:isopropyl alcohol of 90:10 to prepare coating agent B (5 mass%).

[0167] <Example 4> A biaxially oriented polypropylene film A with a thickness of 20 μm was used as the resin substrate, and corona treatment was performed only on the first surface (the surface on the outer layer side). Silica particles with an average particle size of 4 μm were added as an AB agent to the back layer so that the amount was 2000 ppm relative to the total mass of the back layer. A gravure printer was used to coat the first surface of this resin substrate with the mixed solution A of Production Example 3 to form a coating film, which was then dried in an oven at 100° C. for 10 seconds to form a base layer with a thickness of 0.1 μm. Next, a gravure printer was used to coat the coating agent B of Production Example 4 on the formed base layer to form a coating film, which was then dried in an oven at 100° C. for 10 seconds to obtain a gas barrier film of Example 4.

[0168] <Example 5> A gas barrier film of Example 5 was obtained in the same manner as in Example 4, except that the coating amount of Coating Agent B was increased to form a coating thicker than that of Example 4.

[0169] <Example 6> A gas barrier film of Example 6 was obtained in the same manner as in Example 4, except that the coating amount of Coating Agent B was reduced to form a thinner film than in Example 4.

[0170] <Example 7> The first surface of the same resin substrate as used in Example 4 was coated with the mixed solution A of Production Example 3 using a gravure printer to form a coating film, and the coating film was passed through an oven at 100°C for 10 seconds to dry, thereby forming a 0.1 μm thick underlayer. Next, on the formed underlayer, a vacuum deposition device using an electron beam heating method was used to evaporate metallic aluminum, and oxygen gas was introduced thereto to deposit aluminum oxide to form an inorganic oxide layer with a thickness of 20 nm. Further, on the formed inorganic oxide layer, the coating agent B of Production Example 4 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 100°C for 10 seconds to dry, thereby obtaining a gas barrier film of Example 7.

[0171] <Example 8> A gas barrier film of Example 8 was obtained in the same manner as in Example 7, except that the coating amount of Coating Agent B was increased to form a coating thicker than that of Example 7.

[0172] <Example 9> A gas barrier film of Example 9 was obtained in the same manner as in Example 7, except that the coating amount of coating agent B was reduced to form a thinner film than in Example 7.

[0173] <Example 10> Metallic aluminum was evaporated using a vacuum deposition apparatus using an electron beam heating system on the first surface of the same resin substrate as used in Example 4, and oxygen gas was introduced thereto to deposit aluminum oxide to form an inorganic oxide layer having a thickness of 20 nm. Coating agent B of Production Example 4 was then applied onto the inorganic oxide layer formed using a gravure printing machine to form a coating film, which was then passed through an oven at 100°C for 10 seconds to dry, thereby obtaining the gas barrier film of Example 10.

[0174] <Comparative Example 3> A biaxially oriented polypropylene film B with a thickness of 20 μm was used as the resin substrate, and corona treatment was performed only on the first surface (surface on the surface layer side). Polymethyl methacrylate (PMMA) particles with an average particle size of 4 μm were added as an AB agent to the surface layer so that the amount was 1500 ppm relative to the total mass of the surface layer. Silica particles with an average particle size of 4 μm were added as an AB agent to the back layer so that the amount was 2000 ppm relative to the total mass of the back layer. A gravure printer was used to apply the mixed solution A of Production Example 3 to the first surface of this resin substrate to form a coating film, which was then dried in an oven at 100° C. for 10 seconds to form a base layer with a thickness of 0.1 μm. Next, a gravure printer was used to apply the coating agent B of Production Example 4 to the base layer to form a coating film, which was then dried in an oven at 100° C. for 10 seconds to obtain a gas barrier film of Comparative Example 3.

[0175] <Comparative Example 4> A gas barrier film of Comparative Example 4 was obtained in the same manner as in Comparative Example 3, except that the coating amount of Coating Agent B was increased to form a thicker film than that of Comparative Example 3.

[0176] <Comparative Example 5> A gas barrier film of Comparative Example 5 was obtained in the same manner as in Comparative Example 3, except that the coating amount of Coating Agent B was reduced to form a thinner film than in Comparative Example 3.

[0177] <Comparative Example 6> The first surface of the same resin substrate as that used in Comparative Example 3 was coated with the mixed solution A of Production Example 3 using a gravure printer to form a coating film, and the coating film was passed through an oven at 100°C for 10 seconds to dry, thereby forming a 0.1 μm thick undercoat layer. Next, on the formed undercoat layer, a vacuum deposition device using an electron beam heating method was used to evaporate metallic aluminum, and oxygen gas was introduced therein to deposit aluminum oxide to form an inorganic oxide layer with a thickness of 20 nm. Further, on the formed inorganic oxide layer, the coating agent B of Production Example 4 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 100°C for 10 seconds to dry, thereby obtaining a gas barrier film of Comparative Example 6.

[0178] <Comparative Example 7> A gas barrier film of Comparative Example 7 was obtained in the same manner as in Comparative Example 6, except that the coating amount of Coating Agent B was increased to form a coating thicker than that of Comparative Example 6.

[0179] <Comparative Example 8> Metallic aluminum was evaporated using a vacuum deposition apparatus using an electron beam heating system on the first surface of the same resin substrate as used in Comparative Example 3, and oxygen gas was introduced thereto to deposit aluminum oxide to form an inorganic oxide layer having a thickness of 20 nm. Coating agent B of Production Example 4 was then applied onto the inorganic oxide layer formed using a gravure printing machine to form a coating film, which was then dried by passing through an oven at 100°C for 10 seconds to obtain the gas barrier film of Comparative Example 8.

[0180] <Evaluation> -Oxygen barrier properties The gas barrier films obtained in Examples 4 to 10 and Comparative Examples 3 to 8 were measured for oxygen transmission rate (OTR) (cc / (m) in an atmosphere of 30°C and 70% RH using an oxygen transmission rate measuring device (product name: OXTRAN-2 / 20, manufactured by MOCON). 2 ·day·atm) was measured.

[0181] -Water vapor barrier properties The gas barrier films obtained in Examples 4 to 10 and Comparative Examples 3 to 8 were measured for water vapor transmission rate (WVTR) (g / (m) under an atmosphere of 40°C and 90% RH using a water vapor transmission rate measuring device (product name: PERMATRAN-W-3 / 33, manufactured by MOCON). 2 The number of days was measured.

[0182] · Film thickness For the gas barrier films obtained in Examples 4 to 10 and Comparative Examples 3 to 8, the thickness of the film was measured using a scanning electron microscope (product name: JSM6700F, manufactured by JEOL Ltd.). The evaluation results of the Examples are shown in Table 3, and the evaluation results of the Comparative Examples are shown in Table 4.

[0183] [Table 3]

[0184] [Table 4]

[0185] As shown in Table 3, the gas barrier films of Examples 4 to 10 exhibited good oxygen barrier properties. In particular, Examples 4 and 7 exhibited equivalent oxygen barrier properties despite having thinner coating thicknesses than Examples 5 and 8, respectively. The gas barrier film of Comparative Example 3, which contained an AB agent in the surface layer of the resin substrate, was inferior to Examples 4 to 6 in oxygen gas barrier properties. The gas barrier film of Comparative Example 4 had improved oxygen barrier properties due to the thicker coating than that of Comparative Example 3, but the oxygen barrier properties were inferior to those of Examples 4-6. The gas barrier film of Comparative Example 5 had a thinner coating than that of Comparative Example 3, which resulted in poorer oxygen barrier properties. The gas barrier film of Comparative Example 6-8 had poorer oxygen barrier properties than those of Examples 7 to 10. This was believed to be due to the AB agent protruding from the surface layer of the resin substrate, causing defects in the inorganic oxide layer.

[0186] <Production Example 5> 20 g of an aqueous solution of polyacrylic acid having a number average molecular weight of 200,000 (Aron A-10H, manufactured by Toagosei Co., Ltd., solid content concentration 25% by mass) was diluted with 58.9 g of distilled water. Then, 0.44 g of aminopropyltrimethoxysilane (APTMS, manufactured by Aldrich Co.) was added and stirred to prepare a uniform solution, thereby preparing coating solution C.

[0187] <Production Example 6> A mixture D for forming a metal particle layer was obtained by mixing 100 g of an aqueous dispersion of zinc oxide particles (ZE143 manufactured by Sumitomo Osaka Cement Co., Ltd.) and 2 g of a hardener Liofol HAERTER UR 5889-21 (manufactured by Henkel).

[0188] <Example 11> The resin substrate used was the same as that used in Example 4. On the first surface of this resin substrate, the mixed solution A of Production Example 3 was applied using a gravure printer to form a coating film, and the coating film was passed through a 100 ° C. oven for 10 seconds to dry, forming a 0.1 μm thick undercoat layer. Next, the coating solution C of Production Example 5 was applied using a gravure printer to form a coating film on the formed undercoat layer, and the coating film was passed through an 80 ° C. oven for 10 seconds to dry, forming an oxygen barrier film. Next, the mixed solution D of Production Example 6 was applied using a gravure printer to form a coating film on the formed oxygen barrier film, and the coating film was passed through a 50 ° C. oven for 15 seconds to dry, forming a metal particle layer with a thickness of 0.2 μm, thereby obtaining the gas barrier film of Example 11.

[0189] <Example 12> A gas barrier film of Example 12 was obtained in the same manner as in Example 11, except that the coating amount of Coating Liquid C was increased to form a coating thicker than that of Example 11.

[0190] <Example 13> A gas barrier film of Example 13 was obtained in the same manner as in Example 11, except that the coating amount of the coating liquid C was reduced to form a thinner film than that of Example 11.

[0191] <Example 14> The first surface of the same resin substrate as used in Example 11 was coated with the mixed solution A of Production Example 3 using a gravure printer to form a coating film, and the coating film was passed through a 100°C oven for 10 seconds to dry, thereby forming a 0.1 μm thick underlayer. Next, on the formed underlayer, a vacuum deposition device using an electron beam heating method was used to evaporate metallic aluminum, and oxygen gas was introduced therein to deposit aluminum oxide to form an inorganic oxide layer having a thickness of 20 nm. Further, on the formed inorganic oxide layer, the coating solution C of Production Example 5 was coated with a gravure printer to form a coating film, and the coating film was passed through an 80°C oven for 10 seconds to dry, thereby forming an oxygen barrier film. Next, the mixed solution D of Production Example 6 was coated with a gravure printer on the formed oxygen barrier film to form a coating film, and the coating film was passed through a 50°C oven for 15 seconds to dry, thereby forming a metal particle layer having a thickness of 0.2 μm, thereby obtaining a gas barrier film of Example 14.

[0192] <Example 15> A gas barrier film of Example 15 was obtained in the same manner as in Example 14, except that the coating amount of Coating Liquid C was increased to form a coating thicker than that of Example 14.

[0193] <Example 16> A gas barrier film of Example 16 was obtained in the same manner as in Example 14, except that the coating amount of Coating Liquid C was reduced to form a thinner film than that of Example 14.

[0194] <Example 17> On the first surface of the same resin substrate as used in Example 11, a vacuum deposition apparatus using an electron beam heating system was used to evaporate metallic aluminum, and oxygen gas was introduced therein to deposit aluminum oxide to form an inorganic oxide layer having a thickness of 20 nm. Further, on the formed inorganic oxide layer, the coating liquid C of Production Example 5 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 80°C for 10 seconds to dry, thereby forming an oxygen barrier film. Next, the mixed liquid D of Production Example 6 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 50°C for 15 seconds to dry, thereby forming a metal particle layer having a thickness of 0.2 μm, thereby obtaining the gas barrier film of Example 17.

[0195] <Comparative Example 9> The resin substrate used was the same as that used in Comparative Example 3. On the first surface of this resin substrate, the mixed solution A of Production Example 3 was applied using a gravure printer to form a coating film, and the coating film was passed through a 100°C oven for 10 seconds to dry, forming a 0.1 μm thick undercoat layer. Next, the coating solution C of Production Example 5 was applied using a gravure printer to form a coating film on the formed undercoat layer, and the coating film was passed through an 80°C oven for 10 seconds to dry, forming an oxygen barrier film. Next, the mixed solution D of Production Example 6 was applied using a gravure printer to form a coating film on the formed oxygen barrier film, and the coating film was passed through a 50°C oven for 15 seconds to dry, forming a metal particle layer with a thickness of 0.2 μm, thereby obtaining a gas barrier film of Comparative Example 9.

[0196] <Comparative Example 10> A gas barrier film of Comparative Example 10 was obtained in the same manner as in Comparative Example 9, except that the coating amount of Coating Liquid C was increased to form a film thicker than that of Comparative Example 9.

[0197] <Comparative Example 11> A gas barrier film of Comparative Example 11 was obtained in the same manner as in Comparative Example 9, except that the coating amount of Coating Liquid C was reduced to form a thinner film than that of Comparative Example 9.

[0198] <Comparative Example 12> The first surface of the same resin substrate as that used in Comparative Example 9 was coated with the mixed solution A of Production Example 3 using a gravure printer to form a coating film, and the coating film was passed through a 100°C oven for 10 seconds to dry, thereby forming a 0.1 μm thick undercoat layer. Next, on the formed undercoat layer, a vacuum deposition device using an electron beam heating method was used to evaporate metallic aluminum, oxygen gas was introduced therein, and aluminum oxide was deposited to form an inorganic oxide layer having a thickness of 20 nm. Further, on the formed inorganic oxide layer, the coating solution C of Production Example 5 was coated with a gravure printer to form a coating film, and the coating film was passed through an 80°C oven for 10 seconds to dry, thereby forming an oxygen barrier film. Next, the mixed solution D of Production Example 6 was coated with a gravure printer on the formed oxygen barrier film to form a coating film, and the coating film was passed through a 50°C oven for 15 seconds to dry, thereby forming a metal particle layer having a thickness of 0.2 μm, thereby obtaining a gas barrier film of Comparative Example 12.

[0199] <Comparative Example 13> A gas barrier film of Comparative Example 13 was obtained in the same manner as in Comparative Example 12, except that the coating amount of Coating Liquid C was increased to form a coating thicker than that of Comparative Example 12.

[0200] <Comparative Example 14> On the first surface of the same resin substrate as used in Comparative Example 9, a vacuum deposition apparatus using an electron beam heating system was used to evaporate metallic aluminum, and oxygen gas was introduced therein to deposit aluminum oxide to form an inorganic oxide layer having a thickness of 20 nm. Further, on the formed inorganic oxide layer, the coating liquid C of Production Example 5 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 80°C for 10 seconds to dry, thereby forming an oxygen barrier film. Next, the mixed liquid D of Production Example 6 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 50°C for 15 seconds to dry, thereby forming a metal particle layer having a thickness of 0.2 μm, thereby obtaining a gas barrier film of Comparative Example 14.

[0201] The gas barrier films of Examples 7 to 17 and Comparative Examples 6 to 14 were examined assuming that they were used as packaging materials for boiling and retort treatment. <Creating packaging materials for boiling and retorting treatment> A CPP (polypropylene film) was attached to the gas barrier films of Examples 7 to 17 and Comparative Examples 6 to 14 by dry lamination using an adhesive to produce a laminate film assumed to be a packaging material for boiling and retorting treatment having a gas barrier film / adhesive / CPP structure. A multicoater TM-MC manufactured by HIRANO TECSEED was used for dry lamination. The adhesive was placed on the oxygen barrier coating. As the adhesive, a two-liquid curing adhesive Takelac A620 (base agent) / Takenate A65 (curing agent) manufactured by Mitsui Chemicals Polyurethane was used. As the CPP, a polypropylene film Torayfan ZK93KM (60 μm) manufactured by Toray Advanced Film was used. The obtained laminate film was aged at 40° C. for 3 days.

[0202] The laminate film of each example was heat sterilized in hot water at 120° C. for 30 minutes, and the oxygen barrier property and water vapor barrier property were evaluated in the same manner as above. The results after the hot water treatment for Examples 7 to 17 are shown in Table 5, and the results after the hot water treatment for Comparative Examples 6 to 14 are shown in Table 6, respectively. Since Examples 11 to 17 and Comparative Examples 9 to 14 are configured so that the barrier properties are exhibited by hot water treatment, only the data after the hot water treatment are shown.

[0203] [Table 5]

[0204] [Table 6]

[0205] As shown in Table 5, all of the laminate films using the gas barrier films of the Examples showed good oxygen barrier properties after heat sterilization treatment. In particular, Examples 7, 11, and 14 showed comparable oxygen barrier properties despite having thinner films than Examples 8, 12, and 15, respectively. The laminate films using the gas barrier films of the Comparative Examples all had inferior oxygen gas barrier properties after heat sterilization treatment compared to the laminate films using the gas barrier films of the Examples. This was believed to be due to the inclusion of the AB agent in the surface layer of the resin substrate. The gas barrier film of Comparative Example 10 had an improved oxygen barrier property after heat sterilization treatment due to the thicker coating than that of Comparative Example 9, but the oxygen barrier property was inferior to Examples 11-13. The gas barrier film of Comparative Example 11 had a thinner coating than that of Comparative Example 9, and as a result, the oxygen barrier property after heat sterilization treatment deteriorated, and the oxygen barrier property was significantly inferior to those of Examples 11-13. [Industrial Applicability]

[0206] The gas barrier film of the present invention stably exhibits excellent gas barrier properties even under high humidity conditions, and has sufficient adhesion strength and film cohesion strength as a packaging material. Furthermore, the oxygen barrier film can be made thinner, which allows for a reduction in raw material costs. The gas barrier film of the present invention can be suitably used, for example, as a packaging material. By using the gas barrier film of the present invention as a packaging material, the quality retention of the contents can be improved. [Explanation of symbols]

[0207] 1, 20 Resin substrate 1a, 20a front page 1b, 20b second side 4, 24 base layer 5, 25 Film (Oxygen Barrier Film) 6, 26 Antiblocking Agents 10, 200 Gas barrier film 27 Lower stratum 28 Inorganic oxide layer

Claims

1. A resin substrate; an oxygen barrier film formed on a first surface side of the resin substrate; A heat-sealable heat-adhesive layer; Equipped with the oxygen barrier coating contains at least one of a metal alkoxide, a hydrolysate of a metal alkoxide, and a reaction product of a metal alkoxide, and a water-soluble polymer, and does not contain an inorganic layered compound; an inorganic oxide layer is provided between the resin substrate and the oxygen barrier film, the inorganic oxide layer is formed of aluminum oxide or silicon oxide, The resin substrate has two or more resin layers including a base layer, and among the two or more resin layers, a resin layer forming the first surface does not contain an antiblocking agent. Gas barrier film.

2. In the resin substrate, a resin layer forming a second surface opposite to the first surface contains an antiblocking agent. The gas barrier film according to claim 1 .

3. The resin substrate is a polyolefin resin. The gas barrier film according to claim 1 or 2.

4. a base layer between the resin substrate and the inorganic oxide layer, The thickness of the underlayer is 0.01 to 1 μm. The gas barrier film according to claim 1 .

5. a base layer between the resin substrate and the inorganic oxide layer, The underlayer contains an organic polymer as a main component, The organic polymer includes at least one of a polyacrylic resin, a polyol resin, a polyurethane resin, a polyamide resin, or a reaction product of these organic polymers; The gas barrier film according to claim 1 .

6. The inorganic oxide layer has a thickness of 1 to 200 nm. The gas barrier film according to claim 1 .

7. The oxygen barrier coating has a thickness of 0.05 to 1 μm. The gas barrier film according to claim 1 .

8. The oxygen barrier coating further comprises at least one of a silane coupling agent and a reaction product of a silane coupling agent. The gas barrier film according to claim 1 .

9. the oxygen barrier film contains a polyvalent metal salt of a carboxylic acid which is a reaction product between a carboxy group of a polycarboxylic acid polymer and a polyvalent metal compound; The gas barrier film according to claim 1 .

Citation Information

Patent Citations

  • XY table with linear motor

    JP1986076239A

  • Laminate and wrapping container and retort food using laminate

    JP1999227090A

  • Vapor-deposited film laminated packaging material

    JP2000254994A

  • Gas barrier laminate

    JP2001199016A

  • Biaxially stretched polyester film, its manufacturing process and its use

    JP2004130811A